Double-sided adhesive sheet
By using heptyl acrylate as a monomer component, the adhesive force and processability of the double-sided adhesive sheet are improved, and the problems of adhesive performance stability and accuracy in small-area use and cutting processing are solved, so as to achieve Efficient adhesive and processing effect.
Patent Information
- Application Number
- CN202280097965.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-13
- Filing Date
- 2022-12-12
- Publication Date
- 2025-02-14
AI Technical Summary
It is difficult to achieve good fixed adhesive force when used in small areas. At the same time, the adhesive is too soft during cutting and processing, resulting in damage to the stability of the adhesive performance and reduced processing accuracy.
The acrylic polymer containing heptane acrylate as a monomer component is used as the composition of the adhesive layer to ensure that the gel fraction of the adhesive layer is greater than 40%, the energy storage modulus is 0.04 MPa or above at 23°C, and tanδ It is above 0.46 at 23°C.
The high adhesive force of the double-sided adhesive sheet is achieved when used in a small area, and at the same time, it maintains good machining in cutting processing and other cutting processes, alleviates fine concave and convex deformation, and improves the appearance quality.
Smart Images

Figure CN119452057A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a double-sided adhesive sheet.
[0002] This application claims priority based on Japanese Patent Application No. 2022-145688 filed on September 13, 2022, and the entire contents of this application are incorporated herein by reference. Background Art
[0003] Typically, adhesives (also referred to as pressure-sensitive adhesives, the same below) are in a soft solid (viscoelastic) state within a temperature range near room temperature, and have the property of being adhered to an adherend by pressure. Utilizing this property, adhesives are widely used in various industrial fields, from portable electronic devices such as smartphones, home appliances to automobiles, office automation equipment, etc., typically in the form of adhesive sheets containing adhesive layers, for the purposes of bonding components, surface protection, etc. As technical documents related to adhesive sheets, Patent Document 1 and Patent Document 2 can be cited. Patent Document 1 and Patent Document 2 describe adhesives containing acrylic polymers polymerized using heptyl acrylate as a monomer component.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: International Publication No. 2021 / 125247
[0007] Patent Document 2: International Publication No. 2021 / 125278 Summary of the invention
[0008] Problems to be solved by the invention
[0009] Various properties are required for adhesive sheets according to the application site, usage mode, etc. For example, in the fixing of components in portable electronic devices using double-sided adhesive sheets, the adhesive area is usually small due to restrictions on size and weight. The double-sided adhesive sheets used in this application need to have an adhesive force that can achieve good fixing even in a small area. In addition, according to the requirements of lightweight and miniaturization, the performance is required to be at a higher level.
[0010] In addition, the double-sided adhesive sheet used for bonding and fixing can be processed into a prescribed shape (outer shape) in a manner suitable for the shape of the adhesive fixing part, and then used in the form of being pasted to the adherend. For example, in the component fixing of the above-mentioned portable electronic device, the double-sided adhesive sheet is processed into the shape of the adhesive fixing part such as a strip or frame by cutting processing such as punching processing and is used for the fixing of the component. In the double-sided adhesive sheet used in such a form, when the adhesive is too soft, the adhesive protrudes during the cutting process, the stability of the adhesive performance is impaired, or the processing accuracy is reduced, resulting in an undesirable situation. Therefore, the adhesive of the double-sided adhesive sheet used for cutting processing such as punching processing is preferably designed to have sufficient hardness to cope with the above-mentioned processing.
[0011] By the way, double-sided adhesive sheet is usually before use (that is, before being pasted on adherend), considers from viewpoints such as productivity, operability, and processes with the form of the double-sided adhesive sheet with release liner that utilizes release liner to protect each adhesive face.By protecting the adhesive face of double-sided adhesive sheet with release liner, the adhesive face is kept smoothly, can be well adhered to the adherend surface and bring into play desired adhesive properties.In addition, the adhesive sheet with the adhesive face that is protected and kept smoothly by release liner is pasted on adherend equably, can provide good outward appearance under the situation of visual recognition above-mentioned adherend surface.Above-mentioned double-sided adhesive sheet is for example shaped as the reel body (double-sided adhesive sheet reel with release liner) that will be wound up by the double-sided adhesive sheet with release liner that two release liners have protected each adhesive face, circulates, preserves, and is supplied for processing.
[0012] However, in the manufacture of the above-mentioned double-sided adhesive sheet, for example, in the process of winding the double-sided adhesive sheet with a release liner into a roll, sometimes tiny foreign matter is mixed between the two release liners, and due to the pressure in the roll, a depression caused by the foreign matter is generated on the double-sided adhesive sheet. Such a depression also remains as a tiny depression and is visually recognized after the double-sided adhesive sheet is pasted on the adherend, and there is concern that this will cause the appearance quality to decline. When the double-sided adhesive sheet is pasted on the adherend and is stable, the concavo-convex deformation of such a visually recognizable size will not be eliminated. In recent years, in particular, according to the difference in the application parts of the double-sided adhesive sheet such as the display part of an electronic device, there is a tendency to require higher appearance quality, and it is expected that the double-sided adhesive sheet of the fine concavo-convex deformation of the level that was not considered as a problem in the past will be required. If the adhesive is designed to be soft, it is believed that the above-mentioned fine concavo-convex deformation will be alleviated to a certain extent, but on the other hand, there is a worry that the processability during processing such as punching processing is reduced. The suppression of the above-mentioned fine concavo-convex deformation and processability are in a compromise relationship, so it is difficult to take both into account.
[0013] The inventors have conducted intensive research and have completed the present invention by creating a double-sided adhesive sheet that has high adhesive strength suitable for bonding and fixing purposes and can take into account both the relaxation of the above-mentioned fine uneven deformation and processability in punching and the like, by using an acrylic polymer containing heptyl acrylate as a monomer component. That is, the object of the present invention is to provide a double-sided adhesive sheet that has high adhesive strength and can take into account both the relaxation of the above-mentioned fine uneven deformation and processability.
[0014] Means used to solve problems
[0015] According to the present specification, a double-sided adhesive sheet is provided. The double-sided adhesive sheet has an adhesive layer containing an acrylic polymer. The acrylic polymer is a polymer of a monomer component containing heptyl acrylate and a carboxyl-containing monomer. In addition, the monomer component contains more than 3% by weight of the carboxyl-containing monomer. In addition, the gel fraction of the adhesive layer is greater than 40%. Moreover, the storage modulus of the adhesive layer at 23°C is greater than 0.04MPa, and the tanδ at 23°C is greater than 0.46. Here, the tanδ refers to the ratio of the loss modulus G" of the adhesive layer to the storage modulus G' (G" / G').
[0016] By using an acrylic polymer containing heptyl acrylate as a monomer component and containing more than 3% by weight of a carboxyl-containing monomer, the adhesive can have high adhesive force. In addition, the adhesive layer has a composition containing the above-mentioned acrylic polymer, the gel fraction of which is greater than 40%, and the storage modulus at 23°C is more than 0.04MPa, so it has good processability in cutting processes such as punching. In addition, the adhesive layer has a tanδ of more than 0.46 at 23°C, so it has good relaxation, and the fine concavo-convex deformation generated in the adhesive layer such as the depression of the adhesive surface is eliminated or alleviated by the relaxation effect of the adhesive. The above-mentioned storage modulus at 23°C of more than 0.04MPa and tanδ at 23°C of more than 0.46 can be appropriately achieved by using an acrylic polymer containing heptyl acrylate as a monomer component. In short, according to the above-mentioned structure, it is possible to have high adhesive force, and it is possible to take into account the relaxation and processability of fine concavo-convex deformation.
[0017] In some preferred embodiments, the adhesive layer further comprises a tackifying resin. By comprising the tackifying resin, the adhesive force can be improved. As the tackifying resin, at least one selected from a rosin-based tackifying resin and a terpene-based tackifying resin is preferably used.
[0018] In some preferred embodiments, the adhesive layer further comprises an acrylic oligomer. By comprising an acrylic oligomer, the adhesive force can be improved. Among them, it is more preferred to use a tackifying resin and an acrylic oligomer in combination. By using an appropriate amount of a tackifying resin and an acrylic oligomer, a higher adhesive force can be achieved. The technology disclosed herein can achieve excellent adhesive force while taking into account the relaxation and processability of fine concave-convex deformation by using a tackifying resin and an acrylic oligomer in combination. In some embodiments, the content of the tackifying resin is C T Relative to the content C of the above acrylic oligomer O The ratio (C T / C O ) is preferably greater than or equal to 1 and less than or equal to 10.
[0019] In some preferred embodiments, the adhesive composition for forming the adhesive layer contains at least an isocyanate crosslinking agent. By using an isocyanate crosslinking agent, the cohesive force of the adhesive can be appropriately improved.
[0020] In some preferred embodiments, the thickness of the adhesive layer is greater than 5 μm and less than or equal to 50 μm. The adhesive layer with a thickness limited to less than 50 μm can well cope with the requirements of thickness reduction and lightweight. In addition, by making the thickness of the adhesive layer greater than 5 μm, it is easy to eliminate fine concave-convex deformation through the relaxation effect of the adhesive layer. In addition, there is a tendency that the thicker the adhesive layer, the higher the adhesive strength.
[0021] Some preferred embodiments of the double-sided PSA sheet have a 180 degree peel strength to a stainless steel plate (adhesion to SUS) of 10 N / 25 mm or more. A double-sided PSA sheet having such adhesion to SUS can exert high adhesive strength.
[0022] The double-sided adhesive sheet disclosed herein has high adhesive force and good processability in punching and the like, so it can be preferably used for processing into a specified shape and requiring long-term adhesive reliability. For example, it is suitable for fixing components in electronic devices including portable electronic devices such as home appliances, office automation equipment, and smart phones. As described above, according to this specification, an electronic device using any double-sided adhesive sheet disclosed herein is provided, in other words, an electronic device including the double-sided adhesive sheet is provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a cross-sectional view schematically showing the structure of a double-sided PSA sheet according to one embodiment.
[0024] Figure 2 This is a cross-sectional view schematically showing the structure of a double-sided PSA sheet according to another embodiment.
[0025] Figure 3It is a cross-sectional view schematically showing a configuration example of a stacked body.
[0026] Figure 4 It is an exploded perspective view schematically showing a configuration example of a display device. DETAILED DESCRIPTION
[0027] Hereinafter, a preferred embodiment of the present invention will be described. It should be noted that matters other than those specifically mentioned in this specification and required for the implementation of the present invention can be understood by those skilled in the art based on the teachings for the implementation of the invention recorded in this specification and the technical common sense at the time of application. The present invention can be implemented according to the contents disclosed in this specification and the technical common sense in the art. In addition, in the following drawings, the same reference numerals are sometimes used to illustrate components / parts that play the same role, and repeated descriptions are sometimes omitted or simplified. In addition, in order to clearly illustrate the present invention, the embodiments described in the drawings are schematically illustrated and do not necessarily accurately represent the size and scale of the adhesive sheet of the present invention actually provided as a product.
[0028] In this specification, "adhesive" refers to a material that is in a soft solid (viscoelastic) state in the temperature range near room temperature as described above, and has the property of being easily adhered to an adherend by pressure. The so-called adhesive herein is defined as "CADahlquist, "Adhesion: Fundamentals and Practice", McLaren & Sons, (1966) P.143", which generally has a complex tensile elastic modulus E * (1Hz)<10 7 dyne / cm 2 A material having the above properties at 25°C (typically, a material having the above properties at 25°C).
[0029] In this specification, carbon from biomass refers to carbon (renewable carbon) from biomass materials, i.e., materials from renewable organic resources. The above-mentioned biomass materials typically refer to materials from biological resources (typically plants that photosynthesize) that can be continuously reproduced if there is sunlight, water and carbon dioxide source. Therefore, materials (fossil resource materials) from fossil resources that are exhausted after exploitation will be excluded from the concept of biomass materials mentioned here. The biomass carbon ratio of adhesive layer and adhesive sheet, i.e., the proportion of carbon from biomass in the total carbon contained in the adhesive layer and adhesive sheet can be estimated according to the carbon isotope content of the mass number 14 measured by ASTM D6866.
[0030] <Composition of Double-Sided PSA Sheet>
[0031] The double-sided adhesive sheet disclosed herein is constituted by comprising an adhesive layer. The double-sided adhesive sheet can be, for example, a form of a substrate-free double-sided adhesive sheet having a first adhesive face constituted by one surface of the adhesive layer and a second adhesive face constituted by another surface of the adhesive layer. Alternatively, the double-sided adhesive sheet can be a form of a double-sided adhesive sheet with a substrate in which the above-mentioned adhesive layer is laminated on each side of a supporting substrate. Hereinafter, the supporting substrate is sometimes referred to as "substrate". It should be noted that the concept of the adhesive sheet mentioned herein may include articles referred to as adhesive tapes, adhesive labels, adhesive films, etc. It should be noted that the adhesive sheet disclosed herein can be in a roll shape or in a monolithic shape. Alternatively, it can also be an adhesive sheet further processed into a form of various shapes.
[0032] The structure of a double-sided PSA sheet according to one embodiment is schematically shown in Figure 1 The double-sided adhesive sheet 1 is a substrate-free double-sided adhesive sheet composed of an adhesive layer 21. The double-sided adhesive sheet 1 is used by attaching a first adhesive surface 21A composed of one surface (first surface) of the adhesive layer 21 and a second adhesive surface 21B composed of the other surface (second surface) of the adhesive layer 21 to different parts of the adherend. The parts to which the adhesive surfaces 21A and 21B are to be attached may be parts of different components or different parts within a single component. The double-sided adhesive sheet 1 before use (i.e., before being attached to the adherend) may be as follows: Figure 1 The first adhesive surface 21A and the second adhesive surface 21B are shown as components of a double-sided adhesive sheet 100 with a release liner, in which at least one side opposite to the adhesive layer 21 is protected by a release liner 31 and a release liner 32, which are respectively used as the release surface. As the release liner 31 and the release liner 32, for example, a release liner formed by providing a release layer formed by a release treatment agent on one side of a sheet-like substrate (liner substrate) and the single side becomes the release surface can be preferably used. Alternatively, the release liner 32 can be omitted, and a release liner 31 with two sides as the release surface is used, which is overlapped with the double-sided adhesive sheet 1 and wound into a spiral shape, thereby forming a double-sided adhesive sheet with a release liner in a form (roll form) in which the second adhesive surface 21B is in contact with the back side of the release liner 31 and is protected.
[0033] In addition, the double-sided adhesive sheet 100 with a release liner may be Figure 1 The roll body (double-sided PSA sheet roll with release liner) 300 is shown in FIG. Such double-sided PSA sheet roll 300 has a form in which the double-sided PSA sheet 100 with release liner is wound around a core (winding core) 150 .
[0034] The structure of a double-sided PSA sheet according to another embodiment is schematically shown in Figure 2The double-sided adhesive sheet 2 is a double-sided adhesive sheet with a substrate, and the double-sided adhesive sheet with a substrate has: a sheet-like supporting substrate (e.g., a resin film) 10 having a first surface 10A and a second surface 10B; a first adhesive layer 21 fixedly provided on the first surface 10A side; and a second adhesive layer 22 fixedly provided on the second surface 10B side. The double-sided adhesive sheet 2 before use can be as follows Figure 2 The components of the double-sided adhesive sheet 200 with release liner are shown, in which the surface (first adhesive surface) 21A of the first adhesive layer 21 and the surface (second adhesive surface) 22A of the second adhesive layer 22 are protected by release liners 31 and 32. Alternatively, the release liner 32 may be omitted, and a release liner 31 having both sides as release surfaces may be used, and the release liner 31 may be overlapped with the double-sided adhesive sheet 2 and wound into a spiral shape, thereby forming a double-sided adhesive sheet with release liner in a form (roll form) in which the second adhesive surface 22A is in contact with the back surface of the release liner 31 and protected. Such a double-sided adhesive sheet with a substrate is preferred because it is excellent in processability, handling, etc.
[0035] The technology disclosed herein can be preferably implemented in the form of a double-sided adhesive sheet without substrate. Since the double-sided adhesive sheet without substrate does not have a supporting substrate, it is easy to thin layer, and it is also advantageous from the viewpoint of being able to maximize the adhesive properties such as adhesive force and impact resistance. In addition, the double-sided adhesive sheet without substrate can maximize the thickness of the adhesive layer, and relax the fine concavoconvexity produced in the adhesive layer. On the other hand, the double-sided adhesive sheet without substrate is substantially only composed of viscoelastic body, so compared with the double-sided adhesive sheet with substrate, it is disadvantageous in processability, but according to the technology disclosed herein, the viscoelastic properties and gel fraction properties of the adhesive layer are utilized, and good processability can be had.
[0036] <Adhesive Layer>
[0037] (Viscoelastic properties)
[0038] The adhesive layer disclosed herein (in the embodiment having the first adhesive layer and the second adhesive layer, at least one of the first adhesive layer and the second adhesive layer. If not specifically stated, the same shall apply below) has a storage modulus (23°C storage modulus) at 23°C of 0.04MPa or more. The adhesive layer satisfying the above-mentioned 23°C storage modulus has a tendency to suppress the protrusion of the adhesive during cutting processes such as punching and has excellent processability. In some preferred embodiments, the above-mentioned 23°C storage modulus is about 0.06MPa or more, may be 0.08MPa or more, or may be 0.10MPa or more. The adhesive layer having the above-mentioned 23°C storage modulus has moderate cohesion, and therefore has a tendency to easily obtain high adhesive reliability to the adherend, and also has a tendency not to easily produce visually recognizable dimensional concave-convex deformation. In addition, in some embodiments, the 23°C storage modulus of the adhesive layer is about 0.60MPa or less, may be about 0.40MPa or less, or may be about 0.20MPa or less. The adhesive layer having a storage modulus at 23°C of a specified value or less tends to easily obtain adhesion to an adherend. In some preferred embodiments, the storage modulus at 23°C is about 0.18 MPa or less, more preferably 0.15 MPa or less, further preferably 0.13 MPa or less, may be 0.11 MPa or less, may be less than 0.10 MPa, may be 0.08 MPa or less, and may be 0.06 MPa or less.
[0039] In addition, the adhesive layer disclosed herein is characterized in that, in addition to the above-mentioned storage modulus at 23°C being 0.04MPa or more, tanδ (23°C tanδ) at 23°C is 0.46 or more. The above-mentioned tanδ (loss tangent) refers to the ratio of the loss modulus G” of the adhesive layer to the storage modulus G’ of the adhesive layer (G” / G’). An adhesive layer having a tanδ of 0.46 or more at 23°C has good relaxation properties, so fine concave-convex deformations such as depressions on the adhesive surface generated in the adhesive layer are relaxed in a short time by the relaxation effect of the adhesive, thereby eliminating or alleviating. In some embodiments, the above-mentioned 23°C tanδ is 0.50 or more, and can be 0.55 or more. In some preferred embodiments, the above-mentioned 23°C tanδ is 0.60 or more, more preferably 0.65 or more, further preferably 0.70 or more, and particularly preferably 0.75 or more (for example 0.78 or more). Generally, the higher the 23°C storage modulus is, the lower the 23°C tanδ tends to be. Therefore, the upper limit of the 23°C tanδ is preferably an appropriate range that takes into account the 23°C storage modulus. In some embodiments, the 23°C tanδ is less than 3, may be less than 1.5, may be less than 1.2, or may be less than 1.0. From the perspective of taking into account both the easing of concave-convex deformation and the processability based on the 23°C storage modulus, in some preferred embodiments, the 23°C tanδ is less than 1.0, may be less than 0.95, may be less than 0.90, may be less than 0.85, may be less than 0.80, or may be less than 0.75. In other embodiments, the 23°C tanδ may be less than 0.70, may be less than 0.65, may be less than 0.60, or may be less than 0.55.
[0040] In the technology disclosed herein, the 23°C storage modulus and 23°C tanδ of the adhesive layer can be determined by dynamic viscoelasticity. Specifically, a plurality of adhesive layers (double-sided adhesive sheets in the case of double-sided adhesive sheets without substrates) as the object of measurement are overlapped to make an adhesive layer with a thickness of about 2 mm. The adhesive layer is punched into a disc-shaped sample with a diameter of 7.9 mm and fixed between parallel plates, and a dynamic viscoelasticity measurement is performed under the following conditions using a viscoelasticity tester (e.g., manufactured by TA Instruments, ARES or its equivalent) to obtain the 23°C storage modulus and 23°C tanδ.
[0041] ·Measurement mode: Shear mode
[0042] Temperature range: -70℃~150℃
[0043] Heating rate: 5℃ / min
[0044] ·Measurement frequency: 1Hz
[0045] The measurement was also performed by the above method in the Examples described below. It should be noted that as the measurement object, that is, the adhesive layer, a layer formed by applying the corresponding adhesive composition in a layer form and drying or curing it can be used.
[0046] (Acrylic polymer)
[0047] The adhesive layer constituting the double-sided adhesive sheet disclosed herein comprises an acrylic polymer. The above-mentioned adhesive layer is typically an adhesive layer using an acrylic polymer as a base polymer. Such an adhesive layer is also referred to as an acrylic adhesive layer. It should be noted that the base polymer refers to the main component of the rubbery polymer (polymer showing rubber elasticity in the temperature range near room temperature) contained in the adhesive layer. In addition, in this manual, in the absence of special description, "main component" refers to a component that content is greater than 50 weight %. In addition, about the following description of the component that can be contained in adhesive and adhesive layer, if not otherwise specified, it is possible to be applicable to the adhesive composition for forming an adhesive (layer).
[0048] In addition, in this specification, "acrylic polymer" refers to a polymer containing monomer units derived from a monomer having at least one (meth)acryloyl group in one molecule as monomer units constituting the polymer. Hereinafter, a monomer having at least one (meth)acryloyl group in one molecule will also be referred to as an "acrylic monomer". Therefore, the acrylic polymer of this specification is defined as a polymer containing monomer units derived from acrylic monomers. It should be noted that, in this specification, "(meth)acryloyl" is a general term for acryloyl and methacryloyl. Similarly, "(meth)acrylate" is a general term for acrylate and methacrylate, and "(meth)acrylic acid" is a general term for acrylic acid and methacrylic acid.
[0049] As the acrylic polymer used in the technology disclosed herein, a polymer containing a monomer component of heptyl acrylate is used. The acrylic polymer polymerized using a monomer component containing heptyl acrylate is more flexible than the polymer of other alkyl acrylates such as n-butyl acrylate (BA) and 2-ethylhexyl acrylate (2EHA), so the adhesive containing the polymer can adjust 23°C tanδ to a high value, and it is easy to take into account the above-mentioned range of 23°C storage modulus and the above-mentioned range of 23°C tanδ. Heptyl acrylate is considered to be one of the most suitable monomer components for taking into account the above-mentioned 23°C storage modulus and the above-mentioned 23°C tanδ. The reason for the excellent flexibility of the polymer of heptyl acrylate is not particularly restrictive. It is believed that the polymer containing heptyl acrylate as a monomer unit has a relatively large space between the main chains in the adhesive in addition to the low glass transition temperature. Among the heptyl acrylates, n-heptyl acrylate is preferred from the viewpoint of flexibility. The acrylic polymer synthesized by containing n-heptyl acrylate as a monomer component has a relatively long straight-chain side chain, so it is believed that the space between the main chains is easy to become larger.
[0050] In some embodiments, the proportion of heptyl acrylate in the monomer component of the acrylic polymer is, for example, 50% by weight or more (for example, greater than 50% by weight), preferably 70% by weight or more, more preferably 80% by weight or more, further preferably 85% by weight or more, particularly preferably 90% by weight or more (for example, greater than 90% by weight), can be 92% by weight or more, can be 94% by weight or more, can be 95% by weight or more, can be 96% by weight or more. By increasing the amount of heptyl acrylate used, its use effect can be effectively demonstrated (for example, the improvement of tanδ at 23°C of the adhesive, and thus the improvement of the concave-convex deformation relaxation). On the other hand, from the perspective of copolymerizing carboxyl-containing monomers, the proportion of heptyl acrylate in the above-mentioned monomer component is 97% by weight or less. In some preferred embodiments, the proportion of heptyl acrylate in the monomer component is 96% by weight or less, can be 95% by weight or less, and can also be 94% by weight or less. Limiting the proportion of heptyl acrylate within the above range is preferred from the perspective of improving the storage modulus, and is further advantageous from the perspective of improving processability.
[0051] The acrylic polymer may be copolymerized with an alkyl (meth)acrylate other than heptyl acrylate (hereinafter also referred to as "optional alkyl (meth)acrylate"). As the optional alkyl (meth)acrylate, for example, a compound represented by the following formula (1) can be preferably used.
[0052] CH2=C(R 1 )COOR 2 (1)
[0053] Here, R in the above formula (1)1 is a hydrogen atom or a methyl group. 2 is a chain alkyl group having 1 to 20 carbon atoms (wherein R 1 is a hydrogen atom, except for n-heptyl).
[0054] Examples of the optional alkyl (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, amyl (meth)acrylate, isoamyl (meth)acrylate, hexyl (meth)acrylate, heptyl methacrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, and the like. These optional alkyl (meth)acrylates may be used alone or in combination of two or more.
[0055] In some embodiments, the proportion of heptyl acrylate in the total amount of (meth) alkyl acrylate contained in the above-mentioned monomer components is, for example, 50% by weight or more (specifically, 50% to 100% by weight, for example, greater than 50% by weight), preferably 70% by weight or more, more preferably 80% by weight or more, further preferably 90% by weight or more, particularly preferably 95% by weight or more, 99% by weight or more, or 100% by weight. By adopting such a monomer composition, the use effect of heptyl acrylate can be effectively exerted. According to the technology disclosed herein, it is not dependent on optional (meth) alkyl acrylates such as 2EHA and BA. Based on the effect of heptyl acrylate, an adhesive that achieves high adhesion, processability and concave-convex deformation relaxation in a balanced manner can be formed. Therefore, the technology disclosed herein can preferably be implemented in a manner in which the monomer components are substantially free of optional (meth) alkyl acrylates.
[0056] It should be noted that, in the present specification, the monomer component substantially not containing monomer A (such as the optional (meth)acrylate alkyl ester mentioned above) means that the monomer A is at least not used intentionally, and unintentional inclusion of the monomer A in an amount of, for example, about 0.01 wt % or less is allowed.
[0057] In some embodiments, the monomer component may include an alkyl (meth)acrylate having an alkyl group derived from biomass at the ester end (hereinafter also referred to as "biomass (meth)acrylate alkyl ester".). In recent years, environmental issues such as global warming have gradually received attention, and it is expected to reduce the use of fossil resource materials such as petroleum. In such a case, it is also required to reduce the use of fossil resource materials in the field of adhesives. By using biomass (meth)acrylate alkyl ester, an acrylic adhesive that takes into account the suppression of dependence on fossil resource materials can be appropriately realized.
[0058] Biomass (meth) alkyl acrylate is not particularly limited, for example, an ester of an alkanol from biomass and (meth) acrylic acid from biomass or not from biomass. Examples of alkanols from biomass include biomass ethanol, alkanols from plant raw materials such as palm oil or palm kernel oil, coconut oil, castor oil, etc. In the case where the carbon number of the alkanol from biomass is more than 3, the alkanol can be a straight chain or a branched chain. In some embodiments, as a biomass (meth) alkyl acrylate used in the synthesis of acrylic polymers, an ester of an alkanol from biomass and (meth) acrylic acid not from biomass can be used. In the biomass (meth) alkyl acrylate, the more carbon atoms of the alkanol, the higher the proportion of the number of carbons from biomass in the total number of carbons contained in the biomass (meth) alkyl acrylate, that is, the biomass carbon ratio of the (meth) alkyl acrylate. Therefore, in the above-mentioned biomass (meth) alkyl acrylate, from the perspective of reducing the dependence on fossil resource materials, it is desirable that the carbon number of the alkyl from biomass is more. On the other hand, when the carbon number of the alkyl group constituting the alkyl (meth)acrylate is too large, it tends to be difficult to obtain adhesive properties such as adhesive strength, and it may also be disadvantageous from the perspective of synthesis, operability, cost and other productivity. In the method of using an ester of an alkanol derived from biomass and (meth)acrylic acid not derived from biomass as the biomass alkyl (meth)acrylate, it is desirable to use a material that balances adhesive properties with reduced dependence on fossil resource materials (more specifically, the biomass carbon ratio of the above-mentioned alkyl (meth)acrylate).
[0059] In some preferred embodiments, as heptyl acrylate, heptyl acrylate from biomass (biomass heptyl acrylate) is used. By using biomass heptyl acrylate, the effect of the technology disclosed herein can be achieved while reducing the dependence on fossil resource materials. The above-mentioned biomass heptyl ester is an ester of an alkanol from biomass and an acrylic acid from biomass or not from biomass, for example, an ester of an alkanol from biomass and an acrylic acid not from biomass can be used. In this compound, only the heptyl group comes from biomass. As heptyl acrylate from biomass, it is preferred to use n-heptyl acrylate from biomass (biomass n-heptyl acrylate).
[0060] The proportion of the biomass (meth) alkyl acrylate (preferably biomass heptyl acrylate) in the monomer component of the acrylic polymer is, for example, 50% by weight or more (e.g., greater than 50% by weight) in some embodiments, preferably 70% by weight or more, more preferably 80% by weight or more, further preferably 85% by weight or more, particularly preferably 90% by weight or more, and may be 92% by weight or more, 94% by weight or more, or 96% by weight or more. In addition, the proportion of the biomass (meth) alkyl acrylate (preferably biomass heptyl acrylate) in the monomer component is less than 97% by weight, and in some embodiments, may be 95% by weight or less, 93% by weight or less, or 91% by weight or less.
[0061] In addition, the monomer component of the acrylic polymer preferably contains a carboxyl group-containing monomer. The carboxyl group-containing monomer can improve the cohesive force based on its polarity. In addition, when a crosslinking agent such as an isocyanate or epoxy crosslinking agent is used, the carboxyl group can become a crosslinking point of the acrylic polymer. By using a carboxyl group-containing monomer, the 23°C storage modulus of the adhesive layer can be increased, and there is a tendency to easily obtain excellent processability. In addition, by using a carboxyl group-containing monomer, for example, it is possible to exert a more excellent adhesiveness to adherends such as highly polar materials.
[0062] As carboxyl-containing monomers, for example, ethylenically unsaturated monocarboxylic acids such as acrylic acid (AA), methacrylic acid (MAA), carboxylethyl (meth)acrylate, carboxylpentyl (meth)acrylate, crotonic acid, isocrotonic acid, etc.; ethylenically unsaturated dicarboxylic acids such as maleic acid, itaconic acid, and citraconic acid. In addition, the carboxyl-containing monomer may be a monomer of a metal salt (such as an alkali metal salt) having a carboxyl group. The carboxyl-containing monomer may be used alone or in combination of two or more. Among them, AA and MAA may be listed as preferred carboxyl-containing monomers. AA is particularly preferred. When one or more carboxyl-containing monomers are used, the proportion of AA in the above-mentioned carboxyl-containing monomer is preferably 50% by weight or more, more preferably 70% by weight or more, and further preferably 90% by weight or more. In a particularly preferred embodiment, the carboxyl-containing monomer substantially only contains AA. Considering the polarity of the carboxyl group, its role as a crosslinking point, Tg (106°C) and other complex effects, AA is considered to be one of the most suitable monomer materials among the carboxyl group-containing monomers disclosed herein in terms of achieving balanced adhesive properties such as adhesion and cohesion.
[0063] The proportion of the carboxyl-containing monomer in the monomer component of the acrylic polymer is 3% by weight or more (for example, greater than 3.0% by weight), preferably 4.0% by weight or more, more preferably 4.5% by weight or more, further preferably 5.0% by weight or more (for example, greater than 5.0% by weight), particularly preferably 5.5% by weight or more, can be 6.0% by weight or more, can be 6.5% by weight or more, and can also be 7.0% by weight or more. By increasing the amount of carboxyl-containing monomer used, based on the effect of carboxyl-containing monomer, the cohesive force of the adhesive layer is improved, so the 23°C storage modulus and gel fraction of the adhesive can be improved, and an adhesive with excellent processability can be easily obtained. In addition, it is appropriate that the amount of carboxyl-containing monomer is, for example, less than 20% by weight of the monomer component, preferably less than 15% by weight, and more preferably less than 12% by weight. In some preferred embodiments, the amount of the above-mentioned carboxyl-containing monomer can be less than 10% by weight, can be less than 8% by weight, can be less than 6% by weight, and can be less than 5% by weight. By appropriately adjusting the amount of carboxyl-containing monomer used within the above range, an adhesive with good adhesive properties can be easily obtained.
[0064] The acrylic polymer may be copolymerized with a functional group-containing monomer other than the carboxyl group-containing monomer (optional functional group-containing monomer). Examples of the optional functional group-containing monomers that can introduce a functional group that can become a crosslinking group into the acrylic polymer or contribute to the improvement of the adhesive strength include hydroxyl (OH group)-containing monomers (hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; polypropylene glycol mono(meth)acrylate, etc.), acid anhydride group-containing monomers, amide group-containing monomers ((meth)acrylamide, N,N-dimethyl (meth)acrylamide, etc.), amino group-containing monomers (aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, etc.), epoxy group-containing monomers, cyano group-containing monomers, ketone group-containing monomers, monomers having a nitrogen atom-containing ring (N-vinyl-2-pyrrolidone, N-(meth)acryloylmorpholine, etc.), alkoxysilyl group-containing monomers, and imide group-containing monomers. The above optional functional group-containing monomers may be used alone or in combination of two or more.
[0065] In the case where the monomer components constituting acrylic polymers include the above-mentioned optional functional group-containing monomers, the content of the optional functional group-containing monomers in the monomer components is not particularly limited. From the viewpoint of appropriately exerting the effect brought by the use of optional functional group-containing monomers, the content of the optional functional group-containing monomers in the monomer components can be, for example, more than 0.1% by weight, more than 0.5% by weight is appropriate, and can be more than 1% by weight. In addition, for example, in the mode in which the monomer components of acrylic polymers contain heptyl acrylate and carboxyl-containing monomers, from the viewpoint of easily obtaining the balance of adhesive properties in the relationship with these monomer components, the content of the optional functional group-containing monomers in the monomer components is appropriate to be less than 40% by weight, preferably less than 20% by weight, and can also be less than 10% by weight (for example, less than 5% by weight). In some ways, the content of the optional functional group-containing monomers in the monomer components is, for example, less than 3% by weight, can be less than 1% by weight, can be less than 0.5% by weight, can be less than 0.3% by weight, and can also be less than 0.1% by weight. The technology disclosed herein can preferably be implemented in a mode in which the monomer components of acrylic polymers do not substantially include optional functional group-containing monomers.
[0066] In addition, as the above-mentioned optional functional group-containing monomer, a hydroxyl-containing monomer can be used. In this case, it is appropriate that the content of the hydroxyl-containing monomer is about 10% by weight or less (e.g., 0.001% by weight to 10% by weight) in the monomer component, preferably about 5% by weight or less, and more preferably about 2% by weight or less. In some embodiments, the content of the hydroxyl-containing monomer in the monomer component can be, for example, less than 1% by weight, less than 0.5% by weight, less than 0.3% by weight, less than 0.1% by weight, or less than 0.01% by weight. The monomer component of the acrylic polymer may not substantially contain a hydroxyl-containing monomer. In the technology disclosed herein, by limiting the amount of hydroxyl-containing monomer used or not using a composition of hydroxyl-containing monomers, the desired characteristics and effects can be satisfactorily achieved.
[0067] Consider from the viewpoint of effectively bringing into play the effect that makes carboxyl-containing monomer copolymerization, carboxyl-containing monomer is used as the copolymerization component of acrylic acid-based polymer and the shared ratio in the functional group-containing monomer whole (comprising the functional group-containing monomer whole of carboxyl-containing monomer) is suitable for more than 30 weight %, is preferably more than 50 weight %, is more preferably more than 70 weight %, is further preferably more than 80 weight %, is particularly preferably more than 90 weight %, for example can be more than 95 weight %, can be more than 97 weight %, can be more than 98 weight %, can be more than 99 weight % (for example more than 99.9 weight %).The upper limit of the shared ratio of carboxyl-containing monomer in the above-mentioned functional group-containing monomer whole is 100 weight %, for example can be below 95 weight %.
[0068] For the purpose of improving cohesion, the monomer components constituting the acrylic polymer may also contain other copolymer components in addition to the above-mentioned functional group-containing monomers. Examples of other copolymer components include: vinyl ester monomers such as vinyl acetate; aromatic vinyl compounds such as styrene; (meth)acrylic acid cycloalkyl esters such as cyclohexyl (meth)acrylate, cyclopentyl (meth)acrylate, and isobornyl (meth)acrylate; (meth)acrylic acid aryl esters (such as phenyl (meth)acrylate), aryloxyalkyl (meth)acrylate (such as phenoxyethyl (meth)acrylate), and arylalkyl (meth)acrylate (such as benzyl (meth)acrylate) containing aromatic rings (meth)acrylates; olefin monomers; chlorine-containing monomers; isocyanate-containing monomers such as 2-(meth)acryloyloxyethyl isocyanate; alkoxy-containing monomers such as methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate; vinyl ether monomers such as methyl vinyl ether and ethyl vinyl ether; etc. The above-mentioned other copolymer components can be used alone or in combination of two or more.
[0069] The amount of the other copolymer components can be appropriately selected according to the purpose and use, without particular limitation, and from the viewpoint of appropriately exerting the effect brought by its use, it is appropriate to be more than 0.05 weight %, and it can be more than 0.5 weight %. In addition, from the viewpoint of easily obtaining the balance of adhesive performance, it is appropriate that the content of the other copolymer components in the monomer component is less than 20 weight %, and from the viewpoint of appropriately exerting the adhesive properties based on the indispensable monomer component, it is preferably less than 10 weight %, more preferably less than 8 weight %, and further preferably less than 5 weight %, for example, it can be less than 3 weight %, and it can also be less than 1 weight %. The technology disclosed herein can be preferably implemented in a manner that the monomer component does not substantially contain other copolymer components.
[0070] The acrylic polymer may contain a multifunctional monomer having at least two polymerizable functional groups (typically free radical polymerizable functional groups) having unsaturated double bonds such as (meth) acryloyl, vinyl, etc. as other monomer components. By using a multifunctional monomer as a monomer component, the cohesive force of the adhesive layer can be improved. The multifunctional monomer can be used as a crosslinking agent. There is no particular limitation on the multifunctional monomer, and examples thereof include: 1,6-hexanediol di(meth) acrylate, trimethylolpropane tri(meth) acrylate, dipentaerythritol hexa(meth) acrylate, neopentyl glycol di(meth) acrylate, etc. The multifunctional monomer can be used alone or in combination of two or more.
[0071] The usage amount of multifunctional monomers is not particularly limited, and can be appropriately set in a manner to achieve the purpose of use of the multifunctional monomers. The usage amount of multifunctional monomers can be less than about 3 wt % of the above-mentioned monomer components, preferably less than about 2 wt %, more preferably less than about 1 wt % (for example, less than about 0.5 wt %). The lower limit of the usage amount in the case of using multifunctional monomers is not particularly limited as long as it is greater than 0 wt %. Usually, by making the usage amount of multifunctional monomers be more than about 0.001 wt % (for example, more than about 0.01 wt %) of monomer components, the use effect of the multifunctional monomers can be appropriately exerted.
[0072] In a particularly preferred embodiment, as an acrylic polymer, the following acrylic polymer is used: an acrylic polymer synthesized using a monomer component substantially composed of heptyl acrylate (preferably n-heptyl acrylate) and a carboxyl-containing monomer (preferably acrylic acid). According to the above-mentioned monomer composition, the effects of heptyl acrylate and the carboxyl-containing monomer can be effectively exerted, taking into account the specified 23°C storage modulus and 23°C tanδ, and the high adhesive force can be obtained while satisfactorily achieving the balance between concavo-convex deformation relaxation and processability. From such a viewpoint, it is appropriate that the total proportion of heptyl acrylate and the carboxyl-containing monomer in the above-mentioned monomer component is 90% by weight or more (90% by weight to 100% by weight), preferably 95% by weight or more, more preferably 99% by weight or more, further preferably greater than 99.5% by weight, particularly preferably greater than 99.9% by weight (for example, greater than 99.99% by weight), and the total proportion of heptyl acrylate and the carboxyl-containing monomer in the above-mentioned monomer component can be 100% by weight.
[0073] The biomass carbon ratio of the monomer components constituting the acrylic polymer (the biomass carbon ratio of the acrylic polymer) can be, for example, 1% or more, 10% or more is appropriate, preferably 30% or more, more preferably 50% or more (for example, greater than 50%), 70% or more, 80% or more, or 90% to 100%. By designing in this way, an acrylic adhesive can be obtained that takes into account the suppression of dependence on fossil resource materials.
[0074] The method for obtaining the acrylic polymer is not particularly limited, and various polymerization methods known as the synthesis methods of acrylic polymers, such as solution polymerization, emulsion polymerization, bulk polymerization, suspension polymerization, and photopolymerization, can be appropriately adopted. For example, solution polymerization can be preferably adopted. As a monomer supply method when performing solution polymerization, a one-time feeding method of supplying all monomer raw materials at one time, a continuous supply (drip) method, a batch supply (drip) method, etc. can be appropriately adopted. The polymerization temperature can be appropriately selected according to the types of monomers and solvents used, the type of polymerization initiator, etc., and can be, for example, about 20°C to about 170°C (typically about 40°C to about 140°C).
[0075] The solvent (polymerization solvent) used for solution polymerization can be appropriately selected from conventionally known organic solvents. For example, any one solvent or a mixed solvent of two or more selected from aromatic compounds such as toluene (typically aromatic hydrocarbons); acetates such as ethyl acetate; aliphatic or alicyclic hydrocarbons such as hexane and cyclohexane; halogenated alkanes such as 1,2-dichloroethane; lower alcohols such as isopropanol (for example, monohydric alcohols having 1 to 4 carbon atoms); ethers such as tert-butyl methyl ether; ketones such as methyl ethyl ketone, etc. can be used.
[0076] The initiator used for the polymerization can be appropriately selected from the polymerization initiators known in the past according to the type of polymerization method. For example, one or more of the azo polymerization initiators such as 2,2'-azobisisobutyronitrile (AIBN) can be preferably used. As other examples of polymerization initiators, there can be listed: persulfates such as potassium persulfate; peroxide initiators such as benzoyl peroxide (BPO) and hydrogen peroxide; substituted ethane initiators such as phenyl substituted ethane; aromatic carbonyl compounds; etc. As other examples of polymerization initiators, redox initiators based on the combination of peroxides and reducing agents can be listed. Such polymerization initiators can be used alone or in combination of two or more. The amount of the polymerization initiator used can be the usual amount, for example, it can be selected from the range of about 0.005 parts by weight to about 1 part by weight (typically about 0.01 parts by weight to about 1 part by weight) relative to 100 parts by weight of the total monomer components.
[0077] The weight average molecular weight (Mw) of the acrylic polymer is not particularly limited, and an acrylic polymer having an appropriate Mw that can achieve both the above-mentioned 23°C storage modulus and 23°C tanδ can be used. For example, the Mw of the acrylic polymer can be about 10×10 4 ~About 500×10 4 From the viewpoint of adhesive performance, the Mw of the base polymer may be about 20×10 4 Above, it can be about 30×10 4 Above, it can be about 40×10 4 Above, it can also be 50×10 4or more. In some embodiments, the Mw of the acrylic polymer is greater than 600,000, may be greater than 650,000, 700,000 or more is appropriate, and may be 750,000 or more. The larger the Mw of the acrylic polymer, the easier it is to obtain an adhesive showing good cohesion, and there is a tendency for improved processability. In some preferred embodiments, the Mw of the acrylic polymer is greater than 800,000, may be greater than 850,000, may be greater than 900,000, may be greater than 1 million (for example, greater than 1 million), or may be greater than 1.2 million. According to the monomer composition containing heptyl acrylate, it is easy to maintain a low viscosity, so the synthesis of high molecular weight polymers is good, and it is easy to obtain acrylic polymers with the above Mw. In addition, by using an acrylic polymer containing heptyl acrylate as a monomer unit and having a Mw of more than a specified value, it is easy to satisfy the above viscoelastic properties (specifically, 23°C storage modulus and 23°C tanδ) based on the softness of the chemical structure of the polymer and the cohesion based on the molecular weight, and it is possible to satisfactorily balance the relief of uneven deformation and processability. On the other hand, from the perspectives of impact resistance, adhesive strength, ease of synthesis, etc., it is appropriate that the Mw of the acrylic polymer is generally about 3 million or less, preferably 2.5 million or less, more preferably 2 million or less, further preferably 1.8 million or less, and may be 1.5 million or less, or 1.3 million or less. In some preferred embodiments, the Mw of the acrylic polymer may be 1.1 million or less, 1 million or less, 950,000 or less, or 900,000 or less. In other preferred embodiments, the Mw of the acrylic polymer is 800,000 or less, 600,000 or less, less than 500,000, or 450,000 or less. By appropriately limiting the Mw of the acrylic polymer, there is a tendency for tanδ at 23°C to increase and for the relaxation of uneven deformation to increase.
[0078] The Mw of the acrylic polymer can be measured by gel permeation chromatography (GPC) and obtained as a standard polystyrene conversion value. Specifically, it can be measured under the following conditions using a trade name "HLC-8220GPC" (manufactured by Tosoh Corporation) as a GPC measuring device. The same is true in the examples described below.
[0079] [GPC measurement conditions]
[0080] Sample concentration: 0.2 wt% (tetrahydrofuran solution)
[0081] Sample injection volume: 10 μL
[0082] Eluent: Tetrahydrofuran (THF)
[0083] Flow rate: 0.6 mL / min
[0084] Column temperature (measurement temperature): 40°C
[0085] column:
[0086] Sample column: 1 TSKguardcolumn SuperHZ-H + 2 TSKgel SuperHZM-H (manufactured by Tosoh Corporation)
[0087] Reference column: 1 piece, trade name "TSKgel SuperH-RC" (manufactured by Tosoh Corporation)
[0088] Detector: Differential Refractometer (RI)
[0089] Standard sample: polystyrene
[0090] (Tackifying resin)
[0091] In some preferred embodiments, the adhesive layer includes a tackifying resin. By using a tackifying resin, a high adhesive force can be obtained. According to the technology disclosed herein, the adhesive layer becomes an adhesive layer having a prescribed viscoelastic property (specifically, 23°C storage modulus and 23°C tanδ) and a gel fraction by including a composition of a tackifying resin, which can take into account both the easing of uneven deformation and processability. Although not particularly limited, the effect of using a tackifying resin can be effectively exerted in a composition containing a high molecular weight acrylic polymer. As a tackifying resin, there is no particular limitation, for example, various tackifying resins such as rosin tackifying resins, terpene tackifying resins, hydrocarbon tackifying resins, epoxy tackifying resins, polyamide tackifying resins, elastomer tackifying resins, phenol tackifying resins, ketone tackifying resins, etc. can be used. Such tackifying resins can be used alone or in combination of two or more.
[0092] Specific examples of rosin-based tackifying resins include: unmodified rosins (raw rosins) such as gum rosin, wood rosin, and tall oil rosin; modified rosins obtained by modifying these unmodified rosins by hydrogenation, disproportionation, polymerization, etc. (hydrogenated rosin, disproportionated rosin, polymerized rosin, other chemically modified rosins, etc. The same applies hereinafter); various other rosin derivatives; etc. Examples of the above-mentioned rosin derivatives include: rosin esters such as those obtained by esterifying unmodified rosin with alcohols (i.e., esterified rosin), and those obtained by esterifying modified rosin with alcohols (i.e., esterified rosin); unsaturated fatty acid-modified rosins obtained by modifying unmodified rosin and modified rosin with unsaturated fatty acids; unsaturated fatty acid-modified rosin esters obtained by modifying rosin esters with unsaturated fatty acids; rosin alcohols obtained by reducing the carboxyl groups in unmodified rosin, modified rosin, unsaturated fatty acid-modified rosin, or unsaturated fatty acid-modified rosin esters; metal salts of rosins (particularly rosin esters) such as unmodified rosin, modified rosin, and various rosin derivatives; rosin phenol resins obtained by adding phenol to rosins (unmodified rosin, modified rosin, various rosin derivatives, etc.) using an acid catalyst and thermally polymerizing them; etc. Among them, rosin esters are preferred.
[0093] Specific examples of rosin esters include esters of unmodified rosin or modified rosin (hydrogenated rosin, disproportionated rosin, polymerized rosin, etc.), such as methyl ester, triethylene glycol ester, glycerol ester, pentaerythritol ester, etc., but are not particularly limited.
[0094] Examples of terpene tackifier resins include terpene resins such as α-pinene polymers, β-pinene polymers, and pine oil polymers; modified terpene resins obtained by modifying these terpene resins (phenol modification, aromatic modification, hydrogenation modification, hydrocarbon modification, etc.); etc. As an example of the above-mentioned modified terpene resin, terpene phenol resin can be cited.
[0095] Terpene-phenol resin refers to a polymer containing terpene residues and phenol residues, and is a concept that includes copolymers of terpenes and phenolic compounds (terpene-phenol copolymer resins) and resins obtained by phenol-modifying homopolymers or copolymers of terpenes (phenol-modified terpene resins). Specific examples of terpenes constituting such terpene-phenol resins include monoterpenes such as α-pinene, β-pinene, and limonene (including d-form, l-form, and d / l-form (pine oil).) Hydrogenated terpene-phenol resin refers to a hydrogenated terpene-phenol resin having a structure obtained by hydrogenating such a terpene-phenol resin. It is sometimes also called a hydrogenated terpene-phenol resin.
[0096] Examples of hydrocarbon tackifying resins include aliphatic (C5) petroleum resins, aromatic (C9) petroleum resins, aliphatic / aromatic copolymer (C5 / C9) petroleum resins, their hydrogenated products (for example, alicyclic petroleum resins obtained by hydrogenating aromatic petroleum resins), their various modified products (for example, maleic anhydride modified products), coumarone resins, coumarone indene resins and other hydrocarbon resins.
[0097] In some ways, as tackifying resin, at least one selected from rosin tackifying resin and terpene tackifying resin is preferably used. By making the acrylic adhesive contain rosin tackifying resin and / or terpene tackifying resin, the adhesive force can be improved. In some preferred ways, the total proportion of rosin tackifying resin and terpene tackifying resin in the tackifying resin as a whole contained in the adhesive layer can be, for example, greater than about 50% by weight (greater than 50% by weight and less than or equal to 100% by weight), can be about 70% by weight or more, can be about 80% by weight or more, can be about 90% by weight or more, can be 95% by weight or more, and can also be 99% by weight or more.
[0098] As some preferred modes, the above-mentioned tackifying resin includes one or more terpene-phenol resins. The technology disclosed herein can be preferably implemented in a mode in which about 25% by weight or more (more preferably about 30% by weight or more) of the total amount of the tackifying resin is a terpene-phenol resin. The proportion of the terpene-phenol resin in the total amount of the tackifying resin can be about 50% by weight or more, about 70% by weight or more, about 80% by weight or more, or about 90% by weight or more. It can be that substantially all (e.g., about 95% by weight or more and 100% by weight or less, further about 99% by weight or more and 100% by weight or less) of the tackifying resin is a terpene-phenol resin.
[0099] The content of the terpene-phenol resin in the adhesive layer is not particularly limited as long as the target properties (viscoelastic properties, etc.) are met. In some embodiments, from the viewpoint of improving the adhesive force, the content of the terpene-phenol resin is generally about 1 part by weight or more relative to 100 parts by weight of the acrylic polymer, and about 5 parts by weight or more is appropriate, preferably about 8 parts by weight or more, more preferably 10 parts by weight or more, and further preferably about 12 parts by weight or more (for example, 15 parts by weight or more). The more the amount of terpene-phenol resin used, the higher the storage modulus at 23°C. In addition, in some embodiments, the content of the terpene-phenol resin in the adhesive layer is, for example, 70 parts by weight or less, 60 parts by weight or less, 50 parts by weight or less, 40 parts by weight or less, or 30 parts by weight or less relative to 100 parts by weight of the acrylic polymer. In some preferred embodiments, from the viewpoint of improving the ease of uneven deformation of the adhesive, the content of the above-mentioned terpene-phenol resin is less than 30 parts by weight, more preferably 25 parts by weight or less, further preferably 22 parts by weight or less, and 20 parts by weight or less.
[0100] There is no particular restriction on the softening point of the tackifier resin. From the viewpoint of improving cohesive force, it is preferred to use a tackifier resin with a softening point (softening temperature) of about 80°C or more. The softening point of the tackifier resin may be above about 100°C, or above about 110°C. In addition, from the viewpoint of adhesion to the adherend, it is preferred to use a tackifier resin with a softening point of about 200°C or less (more preferably about 180°C or less). In some embodiments, the softening point of the tackifier resin may be less than 160°C, or less than 150°C.
[0101] It should be noted that the softening point of the tackifying resin in this specification is defined as a value measured based on the softening point test method (ring and ball method) specified in JIS K5902 and JIS K2207. Specifically, the sample is quickly melted at the lowest possible temperature and carefully filled into a ring placed on a flat metal plate in a manner that does not form bubbles. After cooling, the raised portion is cut off from the plane containing the upper end of the ring using a slightly heated knife. Next, the support (ring stand) is placed in a glass container (heating bath) with a diameter of more than 85 mm and a height of more than 127 mm, and glycerin is injected to a depth of more than 90 mm. Next, a steel ball (diameter of 9.5 mm, weight of 3.5 g) and a ring filled with the sample are immersed in glycerin in a non-contact manner, and the temperature of the glycerin is maintained at 20°C ± 5°C for 15 minutes. Next, the steel ball is placed in the center of the surface of the sample in the ring and is placed in a fixed position on the support. Next, the distance from the upper end of the ring to the glycerin surface is maintained at 50 mm, and a thermometer is placed so that the center of the mercury ball of the thermometer is at the same height as the center of the ring, and the container is heated. The flame of the Bunsen burner used for heating is brought into contact with the center of the bottom of the container and the middle of the edge to heat evenly. It should be noted that the rate of increase in the bath temperature after reaching 40°C after the start of heating must be 5.0°C ± 0.5°C per minute. Read the temperature when the sample gradually softens and flows down from the ring and finally contacts the bottom plate, and use it as the softening point. Measure more than two softening points at the same time, and use the average value.
[0102] In some embodiments, as the tackifying resin, a tackifying resin T having a softening point of less than 150° C. may be used. L By using tackifying resin T L In some preferred embodiments, the tackifying resin T L The softening point of the tackifier resin T is less than 140°C, more preferably less than 130°C, and further preferably less than 120°C. It may be 110°C or less, 100°C or less, or 90°C or less. L The lower limit of the softening point is not particularly limited. In some embodiments, from the perspective of exerting appropriate cohesive force, the tackifying resin T L The softening point may be, for example, about 50°C or more, 60°C or more, 70°C or more, 80°C or more, 90°C or more, 100°C or more, or 110°C or more.
[0103] As tackifying resin T L , one appropriately selected from the tackifier resins having a softening point of less than 150° C. listed above may be used alone or two or more may be used in combination. In some embodiments, the tackifier resin T LPreferably, it contains at least one selected from rosin-based tackifying resins and terpene-based tackifying resins. L The rosin-based tackifying resin may be contained alone or in combination of two or more rosin-based tackifying resins. L The terpene-based tackifier resin (for example, terpene phenol resin) may be contained alone, or two or more terpene-based tackifier resins may be contained in combination.
[0104] In some embodiments, the terpene tackifying resin (e.g., terpene phenolic resin) is preferably present in the tackifying resin T. L The proportion of the total weight can be, for example, greater than about 50% by weight, about 65% by weight or more, about 75% by weight or more, about 85% by weight or more, or about 95% by weight or more. The technology disclosed herein can preferably be based on the tackifying resin T L The method is implemented in which substantially all (for example, about 97% by weight or more, about 99% by weight or more, and can be 100% by weight) of the terpene tackifying resin is used.
[0105] Although not particularly limited, the tackifying resin T may be preferably L Examples of the rosin-based tackifying resins used include rosin esters such as unmodified rosin esters and modified rosin esters. Preferred examples of modified rosin esters include hydrogenated rosin esters. For example, esters of unmodified rosin or modified rosin (e.g., hydrogenated rosin), such as methyl esters and glycerol esters, can be used as the tackifying resin. L .
[0106] In some embodiments, the tackifying resin T L Hydrogenated rosin esters may be included. In addition, for example, tackifying resin T L Non-hydrogenated rosin esters may be included. Here, non-hydrogenated rosin esters are a concept that collectively represents rosin esters other than hydrogenated rosin esters among the above-mentioned rosin esters. Examples of non-hydrogenated rosin esters include unmodified rosin esters, disproportionated rosin esters, and polymerized rosin esters. Tackifying resin T L The rosin esters may contain a combination of hydrogenated rosin esters and non-hydrogenated rosin esters, may contain only one or two or more hydrogenated rosin esters, or may contain only one or two or more non-hydrogenated rosin esters. In some embodiments, only one or two or more hydrogenated rosin esters may be used as the tackifying resin. L Rosin esters contained in it.
[0107] In addition, as a tackifying resin T LFor example, it may contain a tackifier resin having a softening point of less than 50°C, more preferably below about 40°C (typically a tackifier resin of rosin, terpene, hydrocarbon, etc., such as hydrogenated rosin methyl ester, etc.), or it may not contain it. Such a low softening point tackifier resin may be a liquid tackifier resin that is liquid at 30°C. The liquid tackifier resin may be used alone or in combination of two or more. From the viewpoint of cohesion, etc., the content of the liquid tackifier resin may be tackifier resin T L The total amount is about 30% by weight or less, and appropriately about 10% by weight or less (for example, 0% to 10% by weight), and may be about 2% by weight or less (0.5% to 2% by weight), or may be less than 1% by weight.
[0108] Tackifying resin T L The content of is not particularly limited. In some embodiments, it is appropriate to be about 70 parts by weight or less relative to 100 parts by weight of the acrylic polymer, and may be 60 parts by weight or less, 50 parts by weight or less, 40 parts by weight or less, or 30 parts by weight or less. In some preferred embodiments, relative to 100 parts by weight of the acrylic polymer, the tackifying resin T L The content of the tackifier resin T is less than 30 parts by weight, more preferably less than 25 parts by weight, further preferably less than 22 parts by weight, and may be less than 20 parts by weight. In addition, in some embodiments, from the perspective of improving the adhesive strength, the tackifier resin T is less than 100 parts by weight of the acrylic polymer. L The content of is, for example, 1 part by weight or more, 5 parts by weight or more is appropriate, preferably 8 parts by weight or more, more preferably 10 parts by weight or more, further preferably 12 parts by weight or more, and may be 15 parts by weight or more. L The larger the amount of heptyl acrylate used, the higher the storage modulus at 23° C. The acrylic polymer containing heptyl acrylate as a monomer unit used in the technology disclosed herein has good compatibility with the tackifier resin, so the desired properties can be achieved by containing an appropriate amount of the tackifier resin.
[0109] In some embodiments, the adhesive layer may contain a tackifying resin T in combination within a range that does not impair the effects of the invention. L and a tackifying resin T having a softening point of 150°C or higher (e.g., 150°C to 200°C) H As a tackifying resin T H Among the tackifier resins exemplified above and having a softening point of 150° C. or higher, one type may be used alone or two or more types may be used in combination.
[0110] In some embodiments, the tackifying resin T L Preferably, the tackifier resin accounts for more than 50% by weight of the total amount of the tackifier resin contained in the adhesive layer. Thus, it is easy to effectively express the tackifier resin TL From the perspective of more effectively exerting the effect of using the tackifier resin TL, the tackifier resin T L The proportion of the total amount of the tackifier resin contained in the adhesive layer is preferably 60% by weight or more, more preferably 70% by weight or more, further preferably 80% by weight or more, particularly preferably 90% by weight or more, 95% by weight or more, or 98% by weight or more. In some preferred embodiments, the tackifier resin contained in the adhesive layer substantially only comprises the tackifier resin T L In this method, the tackifying resin T L The ratio of the tackifier resin to the total amount contained in the adhesive layer is in the range of 99% by weight to 100% by weight.
[0111] Although not particularly limited, in some ways, the above-mentioned tackifying resin may include a tackifying resin (such as a terpene phenol resin) having a hydroxyl value greater than 20 mgKOH / g. Wherein, a tackifying resin having a hydroxyl value of more than 30 mgKOH / g is preferred. Hereinafter, a tackifying resin having a hydroxyl value of more than 30 mgKOH / g is sometimes referred to as a "high hydroxyl value resin". According to the tackifying resin comprising such a high hydroxyl value resin, in addition to adhesive force, by interacting with cross-linking agents such as isocyanate cross-linking agents, an adhesive layer with high cohesive force can be achieved. In some ways, the above-mentioned tackifying resin may include a high hydroxyl value resin having a hydroxyl value of more than 60 mgKOH / g (such as more than 70 mgKOH / g). In addition, the above-mentioned high hydroxyl value resin (such as a terpene phenol resin) is preferably used in combination with an acrylic polymer containing heptyl acrylate as a monomer component, and adhesive force and cohesive force can be taken into account.
[0112] The upper limit of the hydroxyl value of the high hydroxyl value resin is not particularly limited. From the viewpoint of compatibility with acrylic polymers, the hydroxyl value of the high hydroxyl value resin is generally about 300 mgKOH / g or less, about 200 mgKOH / g or less is appropriate, preferably about 180 mgKOH / g or less, more preferably about 160 mgKOH / g or less, further preferably about 140 mgKOH / g or less, can be 120 mgKOH / g or less, can be 100 mgKOH / g or less, can also be 80 mgKOH / g or less (for example, 65 mgKOH / g or less). The technology disclosed herein can preferably be implemented in a manner that the tackifying resin includes a high hydroxyl value resin (for example, a terpene tackifying resin, preferably a terpene phenol resin) having a hydroxyl value of 30 mgKOH / g to 160 mgKOH / g. In some ways, a high hydroxyl value resin having a hydroxyl value of 30 mgKOH / g to 80 mgKOH / g (for example, 30 mgKOH / g to 65 mgKOH / g) can be preferably used.
[0113] Here, as the value of the hydroxyl value, there can be adopted a value measured by a potentiometric titration method specified in JIS K0070: 1992. The specific measurement method is as follows.
[0114] [Method for measuring hydroxyl value]
[0115] 1. Reagents
[0116] (1) As the acetylating agent, a reagent obtained by taking about 12.5 g (about 11.8 mL) of acetic anhydride, adding pyridine thereto to make the total amount 50 mL, and stirring thoroughly was used. Alternatively, a reagent obtained by taking about 25 g (about 23.5 mL) of acetic anhydride, adding pyridine thereto to make the total amount 100 mL, and stirring thoroughly was used.
[0117] (2) As a measurement reagent, a 0.5 mol / L potassium hydroxide ethanol solution was used.
[0118] (3) In addition, toluene, pyridine, ethanol and distilled water are prepared.
[0119] 2. Operation
[0120] (1) Accurately weigh about 2 g of the sample in a flat-bottom flask, add 5 mL of the acetylating agent and 10 mL of pyridine, and install an air condenser.
[0121] (2) The flask was heated in a bath at 100°C for 70 minutes, then cooled naturally, 35 mL of toluene was added from the top of the cooling tube as a solvent and stirred, and then 1 mL of distilled water was added and stirred to decompose acetic anhydride. To complete the decomposition, the flask was heated in the bath again for 10 minutes and cooled naturally.
[0122] (3) The condenser was cleaned with 5 mL of ethanol and removed. Then, 50 mL of pyridine was added as a solvent and stirred.
[0123] (4) Use a total volume pipette to add 25 mL of 0.5 mol / L potassium hydroxide ethanol solution.
[0124] (5) Potentiometric titration was performed using a 0.5 mol / L potassium hydroxide ethanol solution. The inflection point of the obtained titration curve was taken as the end point.
[0125] (6) For the blank test, the above (1) to (5) were carried out without adding a sample.
[0126] 3. Calculation
[0127] The hydroxyl value was calculated according to the following formula.
[0128] Hydroxyl value (mgKOH / g) = [(BC) × f × 28.05] / S + D
[0129] Here,
[0130] B: The amount of 0.5 mol / L potassium hydroxide ethanol solution used in the blank test (mL),
[0131] C: The amount of 0.5 mol / L potassium hydroxide ethanol solution used in the sample (mL),
[0132] f: Factor of 0.5 mol / L potassium hydroxide ethanol solution,
[0133] S: weight of the sample (g),
[0134] D: acid value,
[0135] 28.05: 1 / 2 of the molecular weight of potassium hydroxide, 56.11.
[0136] As the high hydroxyl value resin, a resin having a hydroxyl value of more than a specified value among the various tackifying resins mentioned above can be used. One high hydroxyl value resin can be used alone or in combination of two or more. For example, as the high hydroxyl value resin, a terpene phenol resin having a hydroxyl value of more than 30 mgKOH / g can be preferably used. The terpene phenol resin is suitable because the hydroxyl value can be arbitrarily controlled by the copolymerization ratio of phenol.
[0137] Although there is no particular limitation, in the case of using a high hydroxyl value resin, the proportion of the high hydroxyl value resin (e.g., terpene phenol resin) in the overall tackifying resin contained in the adhesive layer can be about 5% by weight or more, 10% by weight or more, 15% by weight or more, or 20% by weight or more. In some embodiments, the proportion of the high hydroxyl value resin in the overall tackifying resin is, for example, preferably about 30% by weight or more. Thus, the effect of using the high hydroxyl value resin can be satisfactorily exerted. In some preferred embodiments, the proportion of the high hydroxyl value resin in the overall tackifying resin is about 40% by weight or more, about 50% by weight or more (e.g., greater than 50% by weight), about 60% by weight or more, about 70% by weight or more, about 80% by weight or more, or about 90% by weight or more. It can be that substantially all of the tackifying resin (e.g., about 95% by weight to about 100% by weight, and further about 99% by weight to about 100% by weight) is a high hydroxyl value resin.
[0138] There is no particular restriction on the softening point of the above-mentioned high hydroxyl resin. The softening point of the high hydroxyl resin may be, for example, above about 50°C. From the viewpoint of improving cohesion, a high hydroxyl resin having a softening point (softening temperature) of above about 80°C may be preferably used. For example, a terpene-phenol resin having such a softening point may be preferably used. The softening point of the high hydroxyl resin may be above about 100°C, or above about 110°C. There is no particular restriction on the upper limit of the softening point of the high hydroxyl resin. From the viewpoint of adhesion to the adherend, a high hydroxyl resin having a softening point of about 200°C or less (more preferably about 180°C or less) may be preferably used. In some embodiments, the softening point of the high hydroxyl resin may be less than 160°C, less than 150°C, less than 145°C, less than 140°C, less than 130°C, or less than 120°C.
[0139] The content of the high hydroxyl value resin in the adhesive layer is not particularly limited as long as it meets the target characteristics (viscoelastic properties, etc.). In some ways, from the viewpoint of improving adhesive force, relative to 100 parts by weight of acrylic polymer, the content of the high hydroxyl value resin is usually about 1 part by weight or more, about 5 parts by weight or more is appropriate, preferably about 8 parts by weight or more, more preferably 10 parts by weight or more, and further preferably about 12 parts by weight or more (for example, 15 parts by weight or more). In addition, in some ways, relative to 100 parts by weight of acrylic polymer, the content of the high hydroxyl value resin in the adhesive layer is, for example, 70 parts by weight or less, can be 60 parts by weight or less, can be 50 parts by weight or less, can be 40 parts by weight or less, and can also be 30 parts by weight or less. In some preferred embodiments, the content of the above-mentioned high hydroxyl value resin is less than 30 parts by weight, more preferably 25 parts by weight or less, further preferably 22 parts by weight or less, and can be 20 parts by weight or less.
[0140] In the case where the adhesive layer disclosed herein includes a tackifying resin, as the tackifying resin, from the viewpoint of increasing the biomass carbon ratio of the adhesive layer, a tackifying resin from a plant (plant-based tackifying resin) can be preferably used. As examples of plant-based tackifying resins, for example, the above-mentioned rosin-based tackifying resins and terpene-based tackifying resins can be cited. Plant-based tackifying resins can be used alone or in combination of two or more. In the case where the adhesive layer disclosed herein includes a tackifying resin, the proportion of the plant-based tackifying resin in the total amount of the tackifying resin is preferably 30% by weight or more (for example, 50% by weight or more, typically 80% by weight or more). In some embodiments, the proportion of the plant-based tackifying resin in the total amount of the tackifying resin is 90% by weight or more (for example, 95% by weight or more, typically 99% to 100% by weight). The technology disclosed herein can preferably be implemented in a manner that does not substantially contain a tackifying resin other than the plant-based tackifying resin.
[0141] The content of the tackifying resin in the adhesive layer is not particularly limited as long as it satisfies the target properties (viscoelastic properties, etc.). In some embodiments, from the viewpoint of improving the adhesive force, the content of the tackifying resin is usually about 1 part by weight or more relative to 100 parts by weight of the acrylic polymer, and it is appropriate to be about 5 parts by weight or more, preferably about 8 parts by weight or more, more preferably 10 parts by weight or more, and further preferably about 12 parts by weight or more (for example, 15 parts by weight or more). There is a tendency that the more the amount of tackifying resin used, the higher the storage modulus at 23°C. In addition, in some embodiments, relative to 100 parts by weight of the acrylic polymer, the content of the tackifying resin in the adhesive layer is, for example, 70 parts by weight or less, 60 parts by weight or less, 50 parts by weight or less, 40 parts by weight or less, and 30 parts by weight or less. In some preferred embodiments, from the viewpoint of the ease of concavo-convex deformation and processability, the content of the above-mentioned tackifying resin is less than 30 parts by weight, more preferably 25 parts by weight or less, further preferably 22 parts by weight or less, and 20 parts by weight or less. The acrylic polymer containing heptyl acrylate as a monomer unit used in the art disclosed herein has good compatibility with a tackifier resin, and therefore desired properties can be achieved by containing an appropriate amount of a tackifier resin.
[0142] (Acrylic oligomer)
[0143] In some preferred embodiments, the adhesive layer contains an acrylic oligomer. By containing an acrylic oligomer, the adhesive force of the adhesive can be improved. According to the technology disclosed herein, in a composition containing an acrylic oligomer, the adhesive layer has high adhesive force and can take into account both concave-convex deformation relaxation and processability. Although not particularly limited, in a composition containing a high molecular weight acrylic polymer, the effect of using an acrylic oligomer can be effectively exerted. One acrylic oligomer can be used alone or in combination of two or more.
[0144] The Tg of the acrylic oligomer is preferably about 0°C or more and about 300°C or less, preferably about 20°C or more and about 300°C or less, and more preferably about 40°C or more and about 300°C or less. By having Tg within the above range, the adhesive force can be appropriately improved. In some preferred embodiments, from the perspective of the cohesiveness of the adhesive, the Tg of the acrylic oligomer is about 30°C or more, more preferably about 50°C or more (for example, about 60°C or more), and from the perspective of adhesion, it is preferably about 200°C or less, more preferably about 150°C or less, and more preferably about 100°C or less (for example, about 80°C or less).
[0145] In this specification, the Tg of the acrylic oligomer refers to the Tg obtained by the Fox equation based on the composition of the above-mentioned monomer components. The Fox equation is shown below and is a relationship between the Tg of the copolymer and the glass transition temperature Tgi of the homopolymer obtained by homopolymerizing the monomers constituting the copolymer.
[0146] 1 / Tg=Σ(Wi / Tgi)
[0147] It should be noted that in the above Fox formula, Tg represents the glass transition temperature of the copolymer (unit: K), Wi represents the weight fraction of monomer i in the copolymer (copolymerization ratio based on weight), and Tgi represents the glass transition temperature of the homopolymer of monomer i (unit: K).
[0148] As the glass transition temperature of the homopolymer used in the calculation of Tg, the value recorded in the known materials can be used. For example, the value recorded in "Polymer Handbook" (3rd edition, John Wiley & Sons, Inc., 1989) can be used. For monomers for which multiple values are recorded in this document, the highest value is adopted.
[0149] For monomers whose homopolymer glass transition temperatures are not described in the above-mentioned documents, values obtained by the following measurement method were used.
[0150] Specifically, 100 parts by weight of monomer, 0.2 parts by weight of 2,2'-azobisisobutyronitrile and 200 parts by weight of ethyl acetate as a polymerization solvent were added to a reactor having a thermometer, a stirrer, a nitrogen inlet tube and a reflux condenser, and stirred for 1 hour while circulating nitrogen. After removing oxygen from the polymerization system, the temperature was raised to 63°C and reacted for 10 hours. Then, it was cooled to room temperature to obtain a homopolymer solution with a solid content concentration of 33% by weight. Then, the homopolymer solution was cast on a release liner and dried to prepare a test sample (sheet-shaped homopolymer) with a thickness of about 2 mm. The test sample was punched into a disc with a diameter of 7.9 mm and clamped between parallel plates. The viscoelasticity was measured by a viscoelasticity testing machine (manufactured by TA Instruments Japan, model name "ARES") in a shear mode in a temperature range of -70°C to 150°C and at a heating rate of 5°C / min while applying a shear strain with a frequency of 1 Hz. The temperature equivalent to the peak temperature of tan δ was taken as the Tg of the homopolymer.
[0151] The weight average molecular weight (Mw) of acrylic oligomers can typically be greater than or equal to about 1000 and less than about 30000, preferably greater than or equal to about 1500 and less than about 20000, and more preferably greater than or equal to about 2000 and less than about 10000. By Mw being within the above range, it is easy to obtain good adhesive force. In some preferred embodiments, the Mw of acrylic oligomers is about 2500 or more (for example, about 3000 or more), and in addition, from the viewpoint of adhesiveness, it is preferably about 7000 or less, more preferably about 5000 or less (for example, about 4500 or less, typically about 4000 or less). The Mw of acrylic oligomers can be measured by gel permeation chromatography (GPC) and obtained in the form of a value converted to standard polystyrene. Specifically, in HPLC8020 manufactured by Tosoh Corporation, TSKgelGMH-H (20) × 2 roots are used as columns and measured with tetrahydrofuran solvent under the condition of a flow rate of about 0.5mL / minute.
[0152] Examples of the monomers constituting the acrylic oligomer include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, and (meth)acrylate. Alkyl (meth)acrylates such as isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, and dodecyl (meth)acrylate; esters of (meth)acrylic acid and alicyclic alcohols such as cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, and tetrahydrodicyclopentadienyl (meth)acrylate ((meth)acrylates containing an alicyclic hydrocarbon group); aryl (meth)acrylates such as phenyl (meth)acrylate and benzyl (meth)acrylate; (meth)acrylates obtained from terpene compound derivative alcohols; etc. Such (meth)acrylates may be used alone or in combination of two or more.
[0153] As the acrylic oligomer, from the viewpoint of being able to further improve the adhesiveness of the adhesive layer, it is preferred to contain, as monomer units, acrylic monomers having a relatively bulky structure, represented by (meth)acrylic acid alkyl esters having a branched alkyl group such as isobutyl (meth)acrylate and tert-butyl (meth)acrylate; esters of (meth)acrylic acid and alicyclic alcohols such as cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, and tetrahydrodicyclopentadienyl (meth)acrylate ((meth)acrylates containing alicyclic hydrocarbon groups); (meth)acrylic acid esters having a cyclic structure such as (meth)acrylic acid aryl esters such as phenyl (meth)acrylate and benzyl (meth)acrylate. In addition, from the viewpoint of being less likely to cause polymerization inhibition when synthesizing the acrylic oligomer or when using ultraviolet rays when preparing the adhesive layer, monomers having a saturated bond are preferred, and (meth)acrylic acid alkyl esters having a branched alkyl group or esters of (meth)acrylic acid and alicyclic alcohols ((meth)acrylates containing alicyclic hydrocarbon groups) can be appropriately used as monomers constituting the acrylic oligomer. It should be noted that the branched alkyl (meth)acrylate, alicyclic (meth)acrylate, and aryl (meth)acrylate described above are equivalent to the (meth)acrylate monomers in the technology disclosed herein. The alicyclic hydrocarbon group may be a saturated or unsaturated alicyclic hydrocarbon group.
[0154] The proportion of (meth)acrylate monomers (e.g., (meth)acrylates containing alicyclic hydrocarbon groups) in the monomer components constituting the acrylic oligomer is typically greater than 50% by weight, preferably greater than 60% by weight, and more preferably greater than 70% by weight (e.g., greater than 80% by weight, and further greater than 90% by weight). In some preferred embodiments, the acrylic oligomer has a monomer composition that substantially only contains (meth)acrylate monomers.
[0155] As the constituent monomer component of the acrylic oligomer, a functional group-containing monomer can be used in addition to the above-mentioned (meth)acrylate monomer. Preferred examples of the above-mentioned functional group-containing monomers include: monomers having a nitrogen atom ring (typically a nitrogen atom-containing heterocyclic ring) such as N-vinyl-2-pyrrolidone and N-acryloylmorpholine; amino group-containing monomers such as (meth)acrylate N,N-dimethylaminoethyl; amide group-containing monomers such as N,N-diethyl (meth)acrylamide; carboxyl group-containing monomers such as AA and MAA; hydroxyl group-containing monomers such as (meth)acrylate 2-hydroxyethyl. These functional group-containing monomers can be used alone or in combination of two or more. Among them, carboxyl group-containing monomers are preferred, and AA is particularly preferred. For example, by using a carboxyl group-containing monomer as a functional group-containing monomer, it is easy to increase the adhesion to a highly polar adherend.
[0156] When the monomer components constituting the acrylic oligomer include functional group-containing monomers, the proportion of the functional group-containing monomers (for example, carboxyl group-containing monomers such as AA) in the above-mentioned monomer components is appropriately about 1% by weight or more, preferably 2% by weight or more, more preferably 3% by weight or more, and is appropriately about 15% by weight or less, preferably 10% by weight or less, more preferably 7% by weight or less.
[0157] Acrylic oligomers can be formed by polymerizing the monomer components constituting the acrylic oligomers. The polymerization method and polymerization mode are not particularly limited, and various polymerization methods known in the past (e.g., solution polymerization, emulsion polymerization, bulk polymerization, photopolymerization, radiation polymerization, etc.) can be used in an appropriate manner. The types of polymerization initiators (e.g., azo polymerization initiators such as AIBN) that can be used as needed are roughly as exemplified in the synthesis of acrylic polymers, and the amount of polymerization initiators and the amount of chain transfer agents such as n-dodecyl mercaptan used arbitrarily are appropriately set in a manner to obtain the desired molecular weight based on technical common sense, so detailed description is omitted here.
[0158] From the above viewpoints, preferred acrylic oligomers include, for example, homopolymers of tetrahydrodicyclopentadienyl methacrylate (DCPMA), cyclohexyl methacrylate (CHMA), isobornyl methacrylate (IBXMA), isobornyl acrylate (IBXA), tetrahydrodicyclopentadienyl acrylate (DCPA), 1-adamantyl methacrylate (ADMA), and 1-adamantyl acrylate (ADA), copolymers of CHMA and isobutyl methacrylate (IBMA), copolymers of CHMA and IBXMA, copolymers of CHMA and N-acryloylmorpholine (ACMO), copolymers of CHMA and diethylacrylamide (DEAA), copolymers of CHMA and AA, copolymers of ADA and methyl methacrylate (MMA), copolymers of DCPMA and IBXMA, and copolymers of DCPMA and MMA.
[0159] In the case of containing acrylic oligomer in the adhesive layer disclosed here, relative to 100 parts by weight of acrylic polymer, its content is, for example, more than 0.1 parts by weight (for example, more than 1 part by weight) is appropriate. From the viewpoint of better exerting the effect of acrylic oligomer, the content of the above-mentioned acrylic oligomer is preferably more than about 3 parts by weight, more preferably more than about 5 parts by weight, can be more than about 8 parts by weight, and can also be more than about 10 parts by weight. In addition, from the viewpoints such as compatibility with acrylic polymer, in some ways, relative to 100 parts by weight of acrylic polymer, the content of the above-mentioned acrylic oligomer is less than 50 parts by weight (for example, less than 40 parts by weight) is appropriate, preferably less than 30 parts by weight, more preferably less than about 25 parts by weight, and further preferably less than about 20 parts by weight. In some preferred ways, relative to 100 parts by weight of acrylic polymer, the content of the above-mentioned acrylic oligomer is less than 20 parts by weight, can be less than 15 parts by weight, can be less than 12 parts by weight, can be less than 10 parts by weight, can be less than 8 parts by weight, and can be less than 6 parts by weight. By setting the usage-amount of the acrylic oligomer to be limited in this way, the effect of the technique disclosed herein can be satisfactorily exhibited.
[0160] In some preferred embodiments, the adhesive layer comprises one or more of the above-mentioned tackifying resins and one or more of the acrylic oligomers. In a composition comprising an acrylic polymer containing heptyl acrylate as a monomer component, by using a tackifying resin and an acrylic oligomer in combination, an adhesive having excellent adhesive strength and high level of both uneven deformation mitigation and processability can be satisfactorily formed. Although not particularly limited, in a composition comprising a high molecular weight acrylic polymer, the effect of using a tackifying resin and an acrylic oligomer in combination can be effectively exerted. The content of the tackifying resin C T [Weight %] relative to the content of acrylic oligomer in the adhesive layer C O [weight %] ratio (C T / C O ) is not particularly limited, and is appropriately, for example, 0.1 or more and 10 or less. In some embodiments, the above ratio (C T / C O ) is 0.25 or more, may be 0.4 or more, may be 0.7 or more, or may be 0.8 or more. T / C O ) is higher, the more effective the addition effect of the tackifying resin can be. In some preferred embodiments, the above ratio (C T / C O) is about 1 or more (e.g., greater than 1.0), more preferably 1.5 or more, further preferably 2.0 or more, 2.5 or more, 3.0 or more, or 3.5 or more. In addition, from the perspective of obtaining the effect of adding acrylic oligomers, in some embodiments, the above ratio (C T / C O ) is about 9 or less, 7 or less is appropriate, can be 5 or less, and can also be 3 or less. In other embodiments, the above ratio (C T / C O ) can be less than 2, can be less than 1.5, or can be less than 1.2.
[0161] In some preferred embodiments, from the viewpoint of satisfactorily exerting the effects of the technology disclosed herein, the combined amount (total amount) of the tackifier resin and the acrylic oligomer contained in the adhesive layer is appropriately about 1 part by weight or more, preferably about 10 parts by weight or more, more preferably about 16 parts by weight or more, further preferably 20 parts by weight or more, and particularly preferably 25 parts by weight or more, relative to 100 parts by weight of the acrylic polymer. In addition, it is appropriately less than 120 parts by weight (for example, about 80 parts by weight or less), preferably less than 60 parts by weight, more preferably about 50 parts by weight or less, further preferably about 40 parts by weight or less, particularly preferably 35 parts by weight or less, and can be 30 parts by weight or less, 28 parts by weight or less, or 26 parts by weight or less.
[0162] In the technology disclosed herein, the total amount (total amount) of the acrylic polymer, tackifying resin and acrylic oligomer in the adhesive layer is appropriately set in a manner to exert the effect of the technology disclosed herein, and is not limited to a specific range. In some preferred modes, from the viewpoint of satisfactorily exerting the effect of the technology disclosed herein, it is appropriate that the total amount (total amount) of the acrylic polymer, tackifying resin and acrylic oligomer in the adhesive layer as a whole is greater than 50% by weight, preferably about 70% by weight or more, more preferably about 90% by weight or more, further preferably 95% by weight or more (e.g., 95% by weight or more and less than 100% by weight or less than 100% by weight), and can be 98% by weight or more.
[0163] (Crosslinking agent)
[0164] In the technology disclosed herein, the adhesive composition used in forming the adhesive layer may contain a crosslinking agent as needed. The type of the crosslinking agent is not particularly limited, and examples thereof include isocyanate crosslinking agents, epoxy crosslinking agents, Azoline crosslinking agent, aziridine crosslinking agent, melamine crosslinking agent, peroxide crosslinking agent, urea crosslinking agent, metal alkoxide crosslinking agent, metal chelate crosslinking agent, metal salt crosslinking agent, carbodiimide crosslinking agent, hydrazine crosslinking agent, amine crosslinking agent, silane coupling agent, etc. The crosslinking agent can be used alone or in combination of two or more. Among them, isocyanate crosslinking agent, epoxy crosslinking agent, Oxazoline crosslinking agents, aziridine crosslinking agents, melamine crosslinking agents, more preferably isocyanate crosslinking agents, epoxy crosslinking agents. By appropriately selecting and using a crosslinking agent, the adhesive layer can obtain a moderate cohesive force, and an adhesive with a balance of adhesive force and cohesive force can be formed. In addition, by increasing the amount of the crosslinking agent used, the gel fraction and the 23°C storage modulus can be increased, and the processability can be improved. It should be noted that the adhesive layer in the technology disclosed herein can contain the above-mentioned crosslinking agent in a form after the crosslinking reaction, a form before the crosslinking reaction, a form of a partial crosslinking reaction, an intermediate or composite form thereof, etc. The above-mentioned crosslinking agent is typically contained in the adhesive layer only in a form after the crosslinking reaction.
[0165] As the isocyanate crosslinking agent, polyfunctional isocyanate (a compound having an average of two or more isocyanate groups per molecule, including a compound having an isocyanurate structure) can be preferably used. The isocyanate crosslinking agent can be used alone or in combination of two or more.
[0166] Examples of the polyfunctional isocyanate include aliphatic polyisocyanates, alicyclic polyisocyanates, and aromatic polyisocyanates.
[0167] Specific examples of aliphatic polyisocyanates include: 1,2-ethylene diisocyanate; 1,2-butylene diisocyanate, 1,3-butylene diisocyanate, 1,4-butylene diisocyanate and other butylene diisocyanates; 1,2-hexylene diisocyanate, 1,3-hexylene diisocyanate, 1,4-hexylene diisocyanate, 1,5-hexylene diisocyanate, 1,6-hexylene diisocyanate, 2,5-hexylene diisocyanate and other hexylene diisocyanates; 2-methyl-1,5-pentane diisocyanate, 3-methyl-1,5-pentane diisocyanate, lysine diisocyanate and the like.
[0168] Specific examples of alicyclic polyisocyanates include isophorone diisocyanate; cyclohexyl diisocyanates such as 1,2-cyclohexyl diisocyanate, 1,3-cyclohexyl diisocyanate, and 1,4-cyclohexyl diisocyanate; cyclopentyl diisocyanates such as 1,2-cyclopentyl diisocyanate and 1,3-cyclopentyl diisocyanate; hydrogenated xylylene diisocyanate, hydrogenated toluene diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated tetramethylxylene diisocyanate, and 4,4'-dicyclohexylmethane diisocyanate.
[0169] Specific examples of aromatic polyisocyanates include 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 2,2'-diphenylmethane diisocyanate, 4,4'-diphenylether diisocyanate, 2-nitrobiphenyl-4,4'-diisocyanate, 2,2'-diphenylpropane-4,4'-diisocyanate, Isocyanate, 3,3'-dimethyldiphenylmethane-4,4'-diisocyanate, 4,4'-diphenylpropane diisocyanate, m-phenylene diisocyanate, p-phenylene diisocyanate, naphthylene 1,4-diisocyanate, naphthylene 1,5-diisocyanate, 3,3'-dimethoxybiphenyl-4,4'-diisocyanate, xylylene-1,4-diisocyanate, xylylene-1,3-diisocyanate, etc.
[0170] As preferred polyfunctional isocyanates, polyfunctional isocyanates having an average of three or more isocyanate groups per molecule can be exemplified. The trifunctional or higher isocyanates can be polymers (typically dimers or trimers) of difunctional or trifunctional or higher isocyanates, derivatives (e.g., addition reaction products of polyols and two or more molecules of polyfunctional isocyanates), polymers, etc. For example, polyfunctional isocyanates such as dimers of diphenylmethane diisocyanate or trimers of diphenylmethane diisocyanate, isocyanurates of hexamethylene diisocyanate (trimer adducts of isocyanurate structures), reaction products of trimethylolpropane and toluene diisocyanate, reaction products of trimethylolpropane and hexamethylene diisocyanate, polymethylene polyphenyl isocyanates, polyether polyisocyanates, polyester polyisocyanates, etc. can be cited. Examples of commercially available products of the polyfunctional isocyanate include "DURANATE TPA-100" manufactured by Asahi Kasei Chemicals, "Coronate L" manufactured by Tosoh Corporation, "Coronate HL" manufactured by Tosoh Corporation, "Coronate HK" manufactured by Tosoh Corporation, "Coronate HX" manufactured by Tosoh Corporation, and "Coronate 2096" manufactured by Tosoh Corporation.
[0171] The technology disclosed herein can be preferably implemented in a manner that at least an isocyanate crosslinking agent is used as a crosslinking agent. The amount of the isocyanate crosslinking agent used is not particularly limited. Relative to 100 parts by weight of the acrylic polymer, the amount of the isocyanate crosslinking agent used, for example, can be about 0.1 parts by weight or more. From the perspective of taking into account both cohesion and adhesion, the amount of the isocyanate crosslinking agent used is generally preferably about 0.3 parts by weight or more (for example, 0.5 parts by weight or more) relative to 100 parts by weight of the acrylic polymer. In some preferred embodiments, the amount of the isocyanate crosslinking agent used relative to 100 parts by weight of the acrylic polymer is about 1.0 parts by weight or more, more preferably about 1.5 parts by weight or more, further preferably about 2.0 parts by weight or more, particularly preferably about 2.5 parts by weight or more, and can be about 2.8 parts by weight or more. By increasing the amount of the isocyanate crosslinking agent used, the gel fraction and the 23°C storage modulus can be increased. In addition, from the viewpoint of improving adhesion to the adherend, the amount of the isocyanate cross-linking agent used is appropriately 10 parts by weight or less, preferably 8 parts by weight or less, more preferably 6 parts by weight or less, further preferably 5 parts by weight or less, particularly preferably 4 parts by weight or less, and can be 3.5 parts by weight or less, or 3.2 parts by weight or less, relative to 100 parts by weight of the acrylic polymer.
[0172] As the epoxy crosslinking agent, a compound having two or more epoxy groups in one molecule can be used without particular limitation. An epoxy crosslinking agent having three to five epoxy groups in one molecule is preferred. The epoxy crosslinking agent can be used alone or in combination of two or more.
[0173] Although not particularly limited, specific examples of epoxy crosslinking agents include N,N,N',N'-tetraglycidyl-m-xylylenediamine, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, polyethylene glycol diglycidyl ether, polyglycerol polyglycidyl ether, etc. Commercial products of epoxy crosslinking agents include "TETRAD-C" and "TETRAD-X" manufactured by Mitsubishi Gas Chemical, "EPICLON CR-5L" manufactured by DIC, "Denacol EX-512" manufactured by Nagase Chemte X, and "TEPIC-G" manufactured by Nissan Chemical Industries, Ltd.
[0174] There is no particular restriction on the amount of epoxy crosslinking agent used. For example, the amount of epoxy crosslinking agent used can be greater than 0 part by weight and less than or equal to about 1 part by weight (typically about 0.001 part by weight to about 1 part by weight) relative to 100 parts by weight of the acrylic polymer. From the viewpoint of properly exerting the effect of improving cohesion, it is usually appropriate for the amount of epoxy crosslinking agent used to be about 0.002 parts by weight or more, preferably about 0.005 parts by weight or more, for example, about 0.01 parts by weight or more, or about 0.02 parts by weight or more. By increasing the amount of epoxy crosslinking agent used, the gel fraction and 23°C storage modulus can be increased. In addition, from the viewpoint of improving the adhesion to the adherend, in some embodiments, the amount of the epoxy crosslinking agent used can be about 0.7 parts by weight or less, about 0.5 parts by weight or less is appropriate, preferably about 0.2 parts by weight or less, more preferably about 0.1 parts by weight or less (for example, less than 0.1 parts by weight), can be 0.07 parts by weight or less, can be 0.04 parts by weight or less, can be 0.03 parts by weight or less. By limiting the amount of the epoxy crosslinking agent used within a specified range, it is easy to maintain sufficient adhesive force.
[0175] In some preferred embodiments, as the crosslinking agent, an isocyanate crosslinking agent and at least one crosslinking agent having a crosslinking functional group different from that of the isocyanate crosslinking agent can be used in combination. In the technology disclosed herein, it can be preferably implemented in a manner of using a crosslinking agent other than an isocyanate crosslinking agent (i.e., a crosslinking agent having a crosslinking reactive group different from that of an isocyanate crosslinking agent, hereinafter also referred to as a "non-isocyanate crosslinking agent") and an isocyanate crosslinking agent in combination.
[0176] The type of non-isocyanate crosslinking agent that can be used in combination with the isocyanate crosslinking agent is not particularly limited, and can be appropriately selected from the above crosslinking agents. The non-isocyanate crosslinking agent can be used alone or in combination of two or more. In some preferred embodiments, an epoxy crosslinking agent can be used as the non-isocyanate crosslinking agent. For example, by using an isocyanate crosslinking agent and an epoxy crosslinking agent in combination, more excellent adhesion properties can be achieved.
[0177] The relationship between the content of the isocyanate crosslinking agent and the content of the non-isocyanate crosslinking agent (preferably the epoxy crosslinking agent) is not particularly limited, and can be appropriately set within the range of satisfying the specified viscoelastic properties and gel fraction. The content of the isocyanate crosslinking agent is, for example, greater than 1 times, can be about 5 times or more, and is appropriately about 10 times or more, preferably about 50 times or more, more preferably about 80 times or more, further preferably about 100 times or more (for example, greater than 100 times), and particularly preferably about 120 times or more (for example, about 140 times or more) relative to the content of the non-isocyanate crosslinking agent (preferably the epoxy crosslinking agent). In addition, from the viewpoint of appropriately exerting the effect obtained by using an isocyanate crosslinking agent in combination with a non-isocyanate crosslinking agent (preferably an epoxy crosslinking agent), the content of the isocyanate crosslinking agent is generally, for example, about 1000 times or less, about 500 times or less, preferably about 300 times or less, more preferably about 200 times or less, and further preferably about 180 times or less (for example, about 160 times or less) relative to the content of the non-isocyanate crosslinking agent (preferably an epoxy crosslinking agent).
[0178] The content of the cross-linking agent in the adhesive composition disclosed herein (the total amount of the cross-linking agent) is not particularly limited. From the viewpoint of cohesion, usually relative to 100 parts by weight of acrylic polymer, the content of the above-mentioned cross-linking agent is about 0.001 parts by weight or more, about 0.01 parts by weight or more is appropriate, preferably about 0.1 parts by weight or more, more preferably about 1 parts by weight or more, further preferably about 2 parts by weight or more, particularly preferably about 2.5 parts by weight or more. In addition, usually relative to 100 parts by weight of acrylic polymer, the content of the cross-linking agent in the adhesive composition is about 20 parts by weight or less, about 15 parts by weight or less is appropriate, preferably about 10 parts by weight or less. In some preferred embodiments, relative to 100 parts by weight of acrylic polymer, the content of the cross-linking agent is 5.0 parts by weight or less, can be 4.0 parts by weight or less, and can also be 3.5 parts by weight or less.
[0179] (Colorant)
[0180] In order to adjust the optical properties (light transmittance, etc.), impart masking properties, design properties, colors, etc., the adhesive layer disclosed herein may or may not contain a colorant. The colorant may be, for example, a colorant of black, gray, white, red, blue, yellow, green, yellow-green, orange, purple, gold, silver, pearl, etc. The above-mentioned colorant may typically be contained in the adhesive layer in a state dispersed in the constituent material of the adhesive layer (or in a dissolved state). As the colorant, conventionally known pigments and dyes may be used. As the pigment, inorganic pigments and organic pigments may be cited. The colorant may be used alone or in combination of two or more.
[0181] There are no particular restrictions on the colorant, and for example, a black colorant can be preferably used because a small amount of it can effectively adjust the masking property and the light-shielding property. Specific examples of black colorants include carbon black, graphite, aniline black, perylene black, cyanine black, titanium black, inorganic pigment hematite, activated carbon, molybdenum disulfide, chromium complex, anthraquinone colorants, etc. The black colorant can be used alone or in combination of two or more.
[0182] In addition, as a colorant, for example, a non-black colorant selected from a white colorant and a gray colorant can also be preferably used. The colorant can be one or more selected from an inorganic material (such as a metal, a metal compound), an organic material, and an organic-inorganic complex. Specific examples of the above-mentioned colorants include: titanium oxide (rutile titanium dioxide, anatase titanium dioxide, etc.), zinc oxide, cerium oxide, aluminum oxide, silicon oxide, zirconium oxide, magnesium oxide, calcium oxide, tin oxide, barium oxide, cesium oxide, yttrium oxide and other metal oxides; carbonate compounds such as magnesium carbonate, calcium carbonate (light calcium carbonate, heavy calcium carbonate, etc.), barium carbonate, zinc carbonate; hydroxides such as aluminum hydroxide, calcium hydroxide, magnesium hydroxide, zinc hydroxide; silicic acid Aluminum, magnesium silicate, calcium silicate and other silicic acid compounds; barium sulfate, calcium sulfate, barium stearate, zinc oxide, zinc sulfide, talc, clay, kaolin, titanium phosphate, mica, gypsum, white carbon black, diatomaceous earth, bentonite, zinc lithopone, zeolite, sericite, hydrated halloysite, etc.; organic materials such as acrylic resin, polystyrene resin, polyurethane resin, amide resin, polycarbonate resin, silicone resin, urea-formaldehyde resin, melamine resin, etc.
[0183] In some ways, the content of the colorant in the adhesive layer (the total amount of more than two kinds of colorants, the total content) is, for example, about 0.1% by weight or more, about 0.5% by weight or more is appropriate, can be about 1% by weight or more, can be about 2% by weight or more, and can also be about 3% by weight or more. In addition, in some ways, from the perspective of maintaining the compatibility with the adhesive component, the adhesive properties such as adhesion, the content of the colorant in the adhesive layer can be about 30% by weight or less, usually about 20% by weight or less is appropriate, can be about 15% by weight or less, can be about 10% by weight or less, can be about 5% by weight or less. In some preferred ways, the content of the colorant in the adhesive layer can be about 3% by weight or less, can be about 1% by weight or less, can be about 0.1% by weight or less, and can also be about 0.01% by weight or less. The technology disclosed herein can preferably be implemented in a manner that the adhesive layer does not substantially contain a colorant.
[0184] (Other additives)
[0185] In addition to the above-mentioned components, the adhesive composition may also contain various additives commonly used in the field of adhesives, such as leveling agents, crosslinking aids, plasticizers, softeners, fillers, antistatic agents, anti-aging agents, ultraviolet absorbers, antioxidants, rust inhibitors, and light stabilizers, as needed. For such various additives, conventionally known substances can be used, which are not the characteristics of the present invention, so detailed description is omitted.
[0186] (Method for forming adhesive layer)
[0187] The adhesive layer (layer containing adhesive) disclosed herein can be an adhesive layer formed by an aqueous adhesive composition, a solvent-based adhesive composition, a hot melt adhesive composition, or an active energy ray-curable adhesive composition. An aqueous adhesive composition refers to an adhesive composition in the form of an adhesive (adhesive layer forming component) contained in a solvent (aqueous solvent) having water as the main component, typically including what is called a water-dispersible adhesive composition (a composition in the form of at least a portion of the adhesive dispersed in water) and the like. In addition, a solvent-based adhesive composition refers to an adhesive composition in the form of an adhesive contained in an organic solvent. As the organic solvent contained in the solvent-based adhesive composition, one or more of the organic solvents (toluene, ethyl acetate, etc.) that can be used in the above-mentioned solution polymerization can be used without particular limitation. The technology disclosed herein can be preferably implemented in a manner having an adhesive layer formed by a solvent-based adhesive composition from the viewpoint of adhesive properties, etc.
[0188] Adhesive layer disclosed herein can be formed by known methods in the past.For example, it is possible to adopt a method for forming adhesive layer by applying adhesive composition on a surface with peelability (peel-off surface) or a non-peel-off surface and drying it.For the double-sided adhesive sheet with the formation of substrate, for example, it is possible to adopt a method (direct method) of directly applying (typically coating) adhesive composition on the substrate and drying it to form adhesive layer.In addition, it is possible to adopt a method (transfer method) of forming adhesive layer on the surface with peelability (peel-off surface), transferring the adhesive layer to the substrate.From the viewpoint of productivity, it is preferred to transfer the adhesive layer.As the above-mentioned peel-off surface, it is possible to utilize the surface of a release liner, the back side of the substrate that has been peeled off, etc.
[0189] The adhesive composition can be applied using a conventionally known coater such as a gravure roll coater, a die coater, or a bar coater. Alternatively, the adhesive composition can be applied by dipping, curtain coating, or the like.
[0190] From the viewpoint of promoting the crosslinking reaction and improving the manufacturing efficiency, the drying of the adhesive composition is preferably carried out under heating. The drying temperature may be, for example, about 40°C to about 150°C, and is generally preferably about 60°C to about 130°C. After the adhesive composition is dried, it may be further aged for the purpose of regulating the migration of components in the adhesive layer, carrying out the crosslinking reaction, relaxing the strain that may exist in the adhesive layer, and the like.
[0191] The adhesive layer may have a single-layer structure or a multi-layer structure having two or more layers. From the viewpoint of productivity, the adhesive layer is preferably a single-layer structure.
[0192] (thickness)
[0193] The thickness of the adhesive layer is not particularly limited, and can be, for example, a composition having an adhesive layer with an appropriate thickness in the range of 0.1 μm to 500 μm, according to the purpose of use, etc. In some ways, from the perspective of avoiding excessive thickening of the double-sided adhesive sheet, the thickness of the adhesive layer is generally about 100 μm or less, preferably about 70 μm or less, more preferably about 60 μm or less, further preferably about 50 μm or less, and can be about 40 μm or less. The thickness of the adhesive layer can be about 35 μm or less, for example, about 30 μm or less, or about 20 μm or less (for example, 15 μm or less). The adhesive layer with limited thickness can well cope with the requirements of thickness thinning and lightweight. In addition, by limiting the thickness of the adhesive layer, it is not easy to produce protrusion of the adhesive during processing such as punching, and the processability can be improved. From the perspective of adhesion to the adherend, in some ways, the lower limit of the thickness of the adhesive layer is about 0.5 μm or more, which is appropriate, can be about 1 μm or more, and is about 3 μm or more. It is advantageous. In some preferred embodiments, the thickness of the adhesive layer is greater than 5 μm, more preferably about 10 μm or more, further preferably about 12 μm or more (for example, greater than 12 μm), further preferably about 15 μm or more, for example, about 18 μm or more. By making the thickness of the adhesive layer greater than 5 μm, it is easy to eliminate fine concave-convex deformations through the relaxation effect of the adhesive layer. In addition, there is a tendency that the greater the thickness of the adhesive layer, the higher the adhesive force. In a further preferred embodiment, the thickness of the adhesive layer can be greater than 20 μm, can be more than 24 μm, can be more than 27 μm, can be about 30 μm or more, can be about 32 μm or more. It should be noted that in a double-sided adhesive sheet with a substrate having a first adhesive layer and a second adhesive layer on each side of the substrate, the first adhesive layer and the second adhesive layer can be the same thickness or different thicknesses from each other.
[0194] (Gel fraction)
[0195] The gel fraction (weight basis) of the adhesive layer disclosed herein is greater than 40%. The adhesive layer with the above-mentioned gel fraction has a tendency to suppress the protrusion of the adhesive and excellent processability in cutting processes such as punching. In addition, the adhesive layer with the above-mentioned gel fraction has a moderate hardness, and therefore has a tendency to be difficult to produce a concave-convex deformation of a visually recognizable size. In some preferred modes, the above-mentioned gel fraction is more than 45%, more preferably more than 50%, more preferably more than 55%, can be more than 60%, can be more than 65%, can be more than 70%, can be more than 75%. In addition, from the viewpoints of adhesive force, it is appropriate that the upper limit of the gel fraction of the adhesive layer is usually less than 90%, can be less than 85%, can be less than 80%, can be less than 75%. In some preferred modes, the gel fraction of the adhesive layer is less than 70%, more preferably less than 65%, further preferably less than 60%, can be less than 55%, can be less than 50%. By limiting the gel fraction of the adhesive layer to below the specified value, there is a tendency to improve the adhesion of the adherend.
[0196] The gel fraction of the adhesive layer is measured by the following method. That is, about 0.1g of the adhesive sample (weight Wg1) is wrapped into a purse shape with a porous polytetrafluoroethylene film (weight Wg2) with an average pore size of 0.2μm, and the bag mouth is tied with a kite line (weight Wg3). As the above-mentioned porous polytetrafluoroethylene (PTFE) film, the trade name "NITOFLON (registered trademark) NTF1122" (average pore size 0.2μm, porosity 75%, thickness 85μm) or its equivalent available from Nitto Denko Corporation is used. The package is immersed in 50mL of ethyl acetate and kept at room temperature (about 23°C) for 7 days, so that only the sol component in the adhesive layer is dissolved outside the above-mentioned film, and then the above-mentioned package is taken out, the ethyl acetate attached to the outer surface is wiped, and the package is dried at 130°C for 2 hours, and the weight (Wg4) of the package is measured. The gel fraction of the adhesive layer is obtained by substituting each value into the following formula.
[0197] Gel fraction (%) = [(Wg4-Wg2-Wg3) / Wg1] × 100
[0198] The measurement was also carried out by the above method in the Examples described later.
[0199] (Biomass Carbon Ratio)
[0200] In some embodiments, the adhesive layer includes a material from biomass, and its biomass carbon ratio can be above a specified value. The biomass carbon ratio of the adhesive layer is, for example, above 1%, above 10%, preferably above 30%, and more preferably above 50%. A high biomass carbon ratio of the adhesive indicates that the amount of fossil resource materials represented by petroleum is small. In this view, the higher the biomass carbon ratio of the adhesive, the more preferred. For example, the biomass carbon ratio of the adhesive layer can be above 55%, above 60%, above 70%, above 75%, above 80%, or greater than 80%. The upper limit of the biomass carbon ratio is defined as 100%, and can be below 99%. From the perspective of the availability of the material, it can be below 95%, or below 90%. From the perspective of easy to exert good adhesive properties, in some embodiments, the biomass carbon ratio of the adhesive layer can be, for example, below 90%, below 85%, or below 80%.
[0201] <Base Material>
[0202] In the form of the double-sided adhesive sheet disclosed herein as a double-sided adhesive sheet with a substrate, as the substrate supporting the adhesive layer, resin film, paper, cloth, rubber sheet, foam sheet, metal foil, their composites, etc. can be used. As examples of paper, Japanese paper, kraft paper, glassine, high-quality paper, synthetic paper, surface coated paper, etc. can be cited. As examples of cloth, woven fabrics, non-woven fabrics, etc. obtained by various fibrous materials alone or in blends, etc. can be cited. As the above-mentioned fibrous materials, examples can be given: cotton, staple fiber, Manila hemp, pulp, rayon, acetate fiber, polyester fiber, polyvinyl alcohol fiber, polyamide fiber, polyolefin fiber, etc. As examples of rubber sheets, natural rubber sheets, butyl rubber sheets, etc. can be cited. As examples of foam sheets, foamed polyolefin sheets, foamed polyurethane sheets, foamed chloroprene rubber sheets, etc. can be cited. As examples of metal foil, aluminum foil, copper foil, etc. can be cited. It should be noted that the substrate is also referred to as a substrate layer in the double-sided adhesive sheet.
[0203] The substrate may be formed of a biomass-derived material or a non-biomass-derived material. From the perspective of producing a double-sided PSA sheet that reduces dependence on fossil resource materials, a biomass-derived substrate material (typically a resin film) is preferably used.
[0204] In addition, the substrate can be a substrate formed using recyclable materials, recycled materials (also referred to as recycled materials). As the recycled material, a resin film can be preferably used. Resin films (such as polyester films such as PET films) can be recycled, so regardless of whether materials from plants are used, continuous reproduction can be carried out by reusing the used resin films, which can reduce the impact on the environment. Such recyclable resin films and recycled resin films are also referred to as recycled films. The above-mentioned recycled materials (such as recycled films) can be formed from materials from biomass, and can also be formed from materials that are not from biomass.
[0205] As the substrate constituting the double-sided adhesive sheet with substrate, it is possible to preferably use a substrate containing a resin film as a base film. The above-mentioned base film is typically a (non-dependent) member that can independently maintain a shape. The substrate in the technology disclosed herein can be substantially composed of such a base film. Alternatively, the above-mentioned substrate can also include an auxiliary layer in addition to the above-mentioned base film. As examples of the above-mentioned auxiliary layers, a colored layer, a reflective layer, a primer layer, an antistatic layer, etc., arranged on the surface of the above-mentioned base film can be cited.
[0206] The resin film is a film having a resin material as a main component (for example, a component with a content greater than 50% by weight in the resin film). Examples of resin films include: polyolefin resin films such as polyethylene (PE), polypropylene (PP), and ethylene-propylene copolymers; polyester resin films such as polyethylene terephthalate (PET), polybutylene terephthalate (PBT), and polyethylene naphthalate (PEN); vinyl chloride resin films; vinyl acetate resin films; polyimide resin films; polyamide resin films; fluorine-containing resin films; cellophane; etc. The resin film may be a rubber film such as a natural rubber film or a butyl rubber film. Among them, from the viewpoint of operability and processability, a polyester film is preferred, and a PET film is particularly preferred.
[0207] It should be noted that, in this specification, "resin film" is typically a non-porous sheet, which is different from the concept of so-called non-woven fabrics and woven fabrics (in other words, it is a concept that does not include non-woven fabrics and woven fabrics). The above-mentioned resin film can be any one of an unstretched film, a uniaxially stretched film, and a biaxially stretched film. In addition, such a resin film can be a non-foamed resin film. Here, a non-foamed resin film refers to a resin film that is not intentionally treated to make a foamed body. Specifically, the non-foamed resin film can be a resin film having a foaming ratio of less than 1.1 times (for example, less than 1.05 times, typically less than 1.01 times).
[0208] The substrate may have transparency, or may have light-shielding properties or light-dimming properties. In some embodiments, a colorant may be contained in the substrate (e.g., a resin film). Thus, the light transmittance (light-shielding properties) of the substrate may be adjusted. Regulating the light transmittance (e.g., vertical light transmittance) of the substrate may help regulate the light transmittance of the substrate, and further help regulate the light transmittance of the double-sided adhesive sheet containing the substrate.
[0209] As the colorant, similar to the colorant that can be contained in the adhesive layer, a pigment or dye known in the past can be used. The colorant is not particularly limited, and for example, it can be a colorant such as black, gray, white, red, blue, yellow, green, yellow-green, orange, purple, gold, silver, pearl.
[0210] In some embodiments, a black colorant may be preferably used as a colorant for the substrate, because a small amount of the colorant can efficiently adjust the light-shielding property (e.g., vertical light transmittance). As specific black colorants, the black colorants exemplified as colorants that may be contained in the adhesive layer may be cited. In some preferred embodiments, a pigment having an average particle size of 10 nm to 500 nm, more preferably 10 nm to 120 nm (e.g., a particulate black colorant such as carbon black) may be used.
[0211] The amount of the colorant used in the substrate (e.g., resin film) is not particularly limited and can be set to an amount appropriately adjusted in a manner that can impart desired optical properties. The amount of the colorant used is appropriately set to about 0.1% by weight to about 30% by weight of the weight of the substrate, for example, 0.1% by weight to 25% by weight (typically 0.1% by weight to 20% by weight).
[0212] The above-mentioned base material (e.g., resin film) may be mixed with various additives such as fillers (inorganic fillers, organic fillers, etc.), dispersants (surfactants, etc.), anti-aging agents, antioxidants, ultraviolet absorbers, antistatic agents, lubricants, plasticizers, etc. as needed. The mixing ratio of various additives may be less than about 30% by weight (e.g., less than about 20% by weight, typically less than about 10% by weight).
[0213] The above-mentioned substrate (e.g., resin film) may be a single-layer structure, or may have a multilayer structure of two, three or more layers. From the viewpoint of shape stability, the substrate is preferably a single-layer structure. In the case of a multilayer structure, it is preferred that at least one layer (preferably all layers) is a layer having a continuous structure of the above-mentioned resin (e.g., polyester resin). The manufacturing method of the substrate (typically a resin film) may appropriately adopt a conventionally known method without particular limitation. For example, conventionally known film forming methods such as extrusion molding, inflation molding, T-die casting molding, and calendering roll molding may be appropriately adopted.
[0214] The substrate can be colored by a colored layer disposed on the surface of a base film (preferably a resin film). In a substrate having a structure including a base film and a colored layer, the base film may contain a colorant or may not contain a colorant. The colored layer may be disposed on any one surface of the base film or may be disposed on both surfaces. In a structure in which colored layers are disposed on both surfaces of the base film, the structures of these colored layers may be the same or different.
[0215] Such a colored layer can be typically formed by coating a colored layer-forming composition containing a colorant and a binder on a base film. As a colorant, pigments and dyes known in the past can be used, as can the colorant that can be contained in the adhesive layer and the resin film. As a binder, materials known in the field of coatings or printing can be used without particular restrictions. For example, polyurethane, phenolic resin, epoxy resin, urea melamine resin, polymethyl methacrylate, etc. can be exemplified. The colored layer-forming composition can be, for example, a solvent-based, ultraviolet curable, thermosetting, etc. The formation of the colored layer can be carried out by the means used in the formation of the colored layer in the past without particular restrictions. For example, a method for forming a colored layer (printed layer) by printing such as gravure printing, flexographic printing, offset printing, etc. can be preferably adopted.
[0216] The colored layer may be a single-layer structure consisting of one layer as a whole, or a multi-layer structure including two, three or more sub-colored layers. A colored layer having a multi-layer structure including two or more sub-colored layers can be formed, for example, by repeatedly applying (e.g., printing) a colored layer-forming composition. The color and amount of the colorant contained in each sub-colored layer may be the same or different. In a colored layer used to impart light-shielding properties, it is particularly meaningful to make a multi-layer structure from the viewpoint of preventing the generation of pinholes and improving the reliability of preventing light leakage.
[0217] The overall thickness of the colored layer is appropriately about 1 μm to about 10 μm, preferably about 1 μm to about 7 μm, for example, about 1 μm to about 5 μm. In a colored layer including two or more sub-colored layers, the thickness of each sub-colored layer is preferably about 1 μm to about 2 μm.
[0218] The surface of the substrate may be subjected to conventionally known surface treatments such as corona discharge treatment, plasma treatment, ultraviolet irradiation treatment, acid treatment, alkali treatment, and application of a primer. Such surface treatments may be used to improve the adhesion between the substrate and the adhesive layer, in other words, the anchoring of the adhesive layer to the substrate.
[0219] In the double-sided adhesive sheet of the method including substrate, the thickness of the substrate is not particularly limited. From the viewpoint of avoiding the double-sided adhesive sheet from becoming too thick, the thickness of the substrate can be, for example, about 200 μm or less, preferably about 150 μm or less, and more preferably about 100 μm or less. According to the purpose and method of use of the double-sided adhesive sheet, the thickness of the substrate can be about 70 μm or less, about 50 μm or less, or about 30 μm or less (for example, about 25 μm or less). In some ways, the thickness of the substrate can be about 20 μm or less, about 15 μm or less, or about 10 μm or less (for example, about 5 μm or less). By reducing the thickness of the substrate, even if the total thickness of the double-sided adhesive sheet is the same, the thickness of the adhesive layer can be further increased, which is advantageous from the viewpoint of improving the adhesion to the adherend and the substrate. In addition, the substrate with limited thickness can well cope with the requirements of thickness reduction and lightweight. From the perspective of the operability (handling) and processability of the double-sided adhesive sheet, the thickness of the substrate is generally about 0.5 μm or more (e.g., 1 μm or more), preferably about 2 μm or more, for example, about 6 μm or more. In some embodiments, the thickness of the substrate can be about 8 μm or more, or about 10 μm or more.
[0220] <Total Thickness of Double-Sided Adhesive Sheet>
[0221] The total thickness of the double-sided adhesive sheet disclosed herein (including an adhesive layer, and may also include a substrate layer, but does not include a release liner.) is not particularly limited. The total thickness of the double-sided adhesive sheet is, for example, about 1 mm or less, can be about 500 μm or less, can be about 300 μm or less, and from the viewpoint of thinning, it is appropriate to be about 200 μm or less, or it can be about 150 μm or less (for example, about 100 μm or less). In some preferred embodiments, the thickness of the double-sided adhesive sheet can be about 50 μm or less, for example, it can be about 35 μm or less. The lower limit of the thickness of the double-sided adhesive sheet is, for example, 0.1 μm or more (for example, 0.5 μm or more), and it is appropriate to be about 3 μm or more, preferably about 10 μm or more, more preferably about 15 μm or more, and further preferably about 20 μm or more, can be about 30 μm or more, or about 50 μm or more. A double-sided adhesive sheet having a thickness above a specified value is easy to obtain adhesion to an adherend, and in addition, it has a tendency to be excellent in operability. In addition, in the double-sided PSA sheet without a substrate, the thickness of the PSA layer is the total thickness of the double-sided PSA sheet.
[0222] <Release liner>
[0223] In the technology disclosed herein, a release liner can be used during the formation of an adhesive layer, the preparation of a double-sided adhesive sheet, the storage, circulation, and shape processing of the double-sided adhesive sheet before use. As a release liner, there is no particular restriction, and for example, a release liner having a release treatment layer on the surface of a liner substrate such as a resin film or paper, a release liner comprising a fluoropolymer (polytetrafluoroethylene, etc.), etc. can be used. The above-mentioned release treatment layer can be formed by, for example, surface treatment of the above-mentioned liner substrate by a release treatment agent such as polysiloxanes, long-chain alkyls, fluorine-containing types, and molybdenum sulfide. As a liner substrate, as with the substrate of the aforementioned double-sided adhesive sheet, a substrate formed using a material from biomass, a recycled material (recovery film, etc.) can be preferably used.
[0224] The release liner disclosed herein (in the embodiment in which the double-sided adhesive sheet with a release liner has two release liners, it is at least one of the two release liners. If not specifically stated, the same shall apply below) can preferably adopt a release liner having a release treatment layer on a release liner substrate. The above-mentioned release treatment layer can be formed by surface-treating the release liner substrate with a release treatment agent. The release treatment agent can be a well-known release treatment agent such as a polysiloxane release treatment agent, a long-chain alkyl release treatment agent, a fluorine-containing release treatment agent, and molybdenum (IV) sulfide. In some embodiments, a release liner having a release treatment layer formed by a polysiloxane release treatment agent can be preferably adopted. The thickness and formation method of the release treatment layer are not particularly limited, and can be set in a manner to exert appropriate releasability on the adhesive side surface of the release liner.
[0225] As the release liner substrate, various plastic films can be used. In this specification, the plastic film is typically a non-porous sheet, which is a concept different from, for example, non-woven fabric (i.e., does not include non-woven fabric). As the release liner substrate, a non-porous structure, typically a resin film substantially free of bubbles (no voids) can be preferably used. The resin film can be a single-layer structure or a multi-layer structure of two or more layers (e.g., a three-layer structure).
[0226] As the material of the above-mentioned plastic film, for example, polyester resins such as polyethylene terephthalate (PET), polybutylene terephthalate (PBT), and polyethylene naphthalate (PEN); polyolefin resins such as polyethylene (PE), polypropylene (PP), ethylene-propylene copolymer, and ethylene-butene copolymer; cellulose resins such as triacetyl cellulose; cyclic polyolefin resins such as acetate resins, polysulfone resins, polyethersulfone resins, polycarbonate resins, polyamide resins, polyimide resins, and norbornene resins, (meth) acrylic resins, polyvinyl chloride resins, polyvinylidene chloride resins, polystyrene resins, polyvinyl alcohol resins, ethylene-vinyl acetate copolymer resins, ethylene-vinyl alcohol copolymer resins, polyarylate resins, and polyphenylene sulfide resins can be listed. A release liner substrate formed by any one of these resins or a mixture of two or more thereof can be used. Among them, as a preferred release liner substrate, a polyester resin film (such as a PET film) formed by a polyester resin can be listed.
[0227] The plastic film used as the release liner substrate may be any one of an unstretched film, a uniaxially stretched film, and a biaxially stretched film. In addition, the plastic film may be a single-layer structure or a multilayer structure including two or more sublayers. The plastic film may be formulated with known additives that can be used for release liner substrates, such as antioxidants, anti-aging agents, heat stabilizers, light stabilizers, ultraviolet absorbers, pigments, dyes and other colorants, lubricants, fillers, antistatic agents, slip agents, anti-blocking agents, and nucleating agents. In the plastic film with a multilayer structure, each additive may be formulated in all sublayers or in only a portion of the sublayers.
[0228] The thickness of the release liner is not particularly limited, for example, it can be about 10 μm to about 500 μm. From the perspective of the strength and dimensional stability of the release liner, it is appropriate that the thickness of the release liner is more than 20 μm, preferably more than 25 μm, more than 30 μm, or more than 35 μm. By using a release liner with sufficient thickness to protect the adhesive surface, it is easy to maintain the smoothness of the adhesive surface. For example, it is not easy to produce a phenomenon of uneven deformation in the adhesive layer due to external forces from the back of the release liner, foreign matter present on the back of the release liner, etc. Such a phenomenon can be, for example, a phenomenon caused by foreign matter mixed between the release liners when the double-sided adhesive sheet with a release liner is wound into a roll. In addition, from the perspective of the operability of the release liner (such as ease of winding), it is appropriate that the thickness of the release liner is less than 300 μm, preferably less than 200 μm, less than 150 μm, or less than 100 μm. By having a thickness of the release liner below a specified value, it is easy to remove the double-sided adhesive sheet smoothly. In some embodiments, the thickness of the release liner can be 75 μm or less, 60 μm or less, 50 μm or less, 40 μm or less, or 30 μm or less. According to the technology disclosed herein, even in the case where a fine concave-convex deformation such as a depression is generated in the adhesive layer due to an external force, a foreign body, etc. from the back of the release liner, the adhesive layer has excellent concave-convex deformation mitigation, so the fine concave-convex deformation can be eliminated or alleviated, and good appearance quality can be given. It should be noted that in the case where the double-sided adhesive sheet with a release liner disclosed herein has two release liners, i.e., a first release liner and a second release liner, the thickness of the first release liner and the second release liner can be the same or different. From the perspective of peeling operability, the first release liner and the second release liner preferably have different thicknesses, and the thickness of the thicker release liner preferably has a thickness of about 1.1 times or more, for example, about 1.25 times or more, of the thickness of the thinner release liner.
[0229] <Roll body>
[0230] In addition, according to this specification, a roll body (double-sided adhesive sheet roll with release liner) containing the double-sided adhesive sheet with release liner disclosed herein in a wound form is provided. The concavoconvex deformation relaxation property, which is one of the effects of the technology disclosed herein, is effective for the fine concavoconvex deformation of the adhesive layer caused by the tiny foreign matter mixed between the two release liners when the double-sided adhesive sheet with release liner is wound into a roll. The technology disclosed herein is suitable for double-sided adhesive sheets stored in the form of a roll body before use. The roll body as described above typically includes a core (roll core) and a double-sided adhesive sheet with release liner wound around the core. The shape of the core is not particularly limited, for example, it can be a solid cylindrical, a hollow cylindrical (i.e., cylindrical), a hollow or solid polygonal column; etc. From the viewpoint of improving the operability of the roll body, a hollow cylindrical or hollow polygonal column-shaped core can be preferably used. A cylindrical core is particularly preferred.
[0231] <Characteristics of Double-Sided Adhesive Sheets>
[0232] (Adhesion to SUS)
[0233] In some embodiments, the 180-degree peel strength (adhesion to SUS) of the double-sided adhesive sheet to the stainless steel plate is preferably about 10N / 25mm or more. The double-sided adhesive sheet with the above-mentioned adhesion to SUS can exert high adhesive force. The above-mentioned adhesion to SUS is more preferably about 15N / 25mm or more, further preferably about 18N / 25mm or more, and particularly preferably 20N / 25mm or more (for example, 22N / 25mm or more). There is no particular restriction on the upper limit of the above-mentioned adhesion to SUS. From the perspective of taking into account processability, it can usually be about 50N / 25mm or less, and in some embodiments, it can be about 30N / 25mm or less. Regarding the above-mentioned adhesion to SUS, a SUS plate is used as the adherend, and the measurement is carried out under the conditions of a tensile speed of 300mm / minute and a peeling angle of 180 degrees under the measurement environment of 23°C and 50%RH. More specifically, it is measured by the method described in the embodiments described later.
[0234] (Biomass Carbon Ratio)
[0235] In some ways, the double-sided adhesive sheet includes a material from biomass, and its biomass carbon ratio can be above a specified value. The biomass carbon ratio of the double-sided adhesive sheet is, for example, 1% or more, 10% or more, preferably 30% or more, and more preferably 50% or more. The high biomass carbon ratio of the double-sided adhesive sheet indicates that the amount of fossil resource materials represented by petroleum is small. In this view, the higher the biomass carbon ratio of the double-sided adhesive sheet, the more preferred. For example, the biomass carbon ratio of the double-sided adhesive sheet can be 55% or more, 60% or more, 70% or more, 75% or more, 80% or more, or greater than 80%. The upper limit of the biomass carbon ratio is defined as 100%, which can be 99% or less. From the perspective of the availability of the material, it can be 95% or less, or 90% or less. From the perspective of easy to play a good adhesive performance, in some ways, the biomass carbon ratio of the double-sided adhesive sheet can be, for example, 90% or less, 85% or less, or 80% or less.
[0236] <Purpose>
[0237] The purpose of the double-sided adhesive sheet disclosed herein is not particularly limited and can be used for various purposes. The double-sided adhesive sheet disclosed herein requires high adhesive force, which is suitable for the adhesive fixation of the member in the purpose that can be processed into a specified shape (outline). For example, it can be preferably used for the purpose of fixing the member in various portable devices (portable devices). In addition, the concavo-convex deformation of the adhesive layer such as the depression on the adhesive layer surface of the double-sided adhesive sheet disclosed herein is highly suppressed, so it is suitable for the purposes of requiring appearance quality such as the visual recognition of the double-sided adhesive sheet pasted on the adherend surface. For example, according to the application part of the double-sided adhesive sheet such as the display part of an electronic device, there is a tendency to require higher appearance quality. The double-sided adhesive sheet disclosed herein is suitable for the fixing of the member in the display part of an electronic device such as the above-mentioned portable electronic device.
[0238] Non-limiting examples of the portable electronic devices include: mobile phones, smart phones, tablet personal computers, notebook personal computers, various wearable devices (for example, wrist-worn devices such as watches, modular devices such as those worn on a part of the body with clips, straps, etc., eyewear devices such as glasses (monocular, binocular, and helmet-type), clothing devices such as those worn on shirts, socks, hats, etc. in the form of accessories, and ear-worn devices such as headphones), digital cameras, digital video cameras, audio equipment (portable music players, voice recorders, etc.), calculators (desktop calculators, etc.), portable game devices, electronic dictionaries, electronic notepads, electronic books, in-vehicle information devices, portable radios, portable televisions, portable printers, portable scanners, portable modems, etc. It should be noted that in this specification, "portable" is not sufficient to be interpreted as merely portable, and it essentially has a level of portability that can be carried relatively easily by an individual (a standard adult). Examples of the electronic devices include personal computers (desktop, notebook, tablet, etc.), televisions, etc. These electronic devices may include electronic devices having a display device (display device) such as liquid crystal or organic electroluminescence.
[0239] In some embodiments, the double-sided adhesive sheet is used, for example, for the purpose of fixing the pressure-sensitive sensor to other components in the portable electronic device having the pressure-sensitive sensor in the above-mentioned portable electronic device. In some embodiments, the double-sided adhesive sheet can be used to fix the pressure-sensitive sensor to other components in an electronic device (typically a portable electronic device) having a function of specifying an absolute position on a board (typically a touch panel) corresponding to the screen by means for indicating a position on the screen (typically a pen-type, mouse-type device) and means for detecting the position.
[0240] In addition, in some preferred embodiments, the double-sided adhesive sheet is suitable for use on the back of a display screen (display unit) such as a touch panel display configured in a portable electronic device. By configuring the double-sided adhesive sheet of some preferred embodiments on the back of the above-mentioned display screen (display unit), regardless of how the portable electronic device is used, the reduction in the visual recognition of the display screen can be prevented.
[0241] As the material (adherend material) to be pasted on the double-sided adhesive sheet disclosed herein, although there is no particular limitation, for example, metal materials such as copper, silver, gold, iron, tin, palladium, aluminum, nickel, titanium, chromium, zinc, etc. or alloys containing two or more of them, such as polyimide resins, acrylic resins, polyether nitrile resins, polyether sulfone resins, polyester resins (PET resins, polyethylene naphthalate resins, etc.), polyvinyl chloride resins, polyphenylene sulfide resins, polyether ether ketone resins, polyamide resins (so-called aromatic polyamide resins, etc.), polyarylate resins, polycarbonate resins, various resin materials such as liquid crystal polymers (typically plastic materials), alumina, zirconium oxide, soda-lime glass, quartz glass, carbon, etc. Inorganic materials, etc., are widely used. Among them, metal materials such as copper, aluminum, stainless steel, polyester resins such as PET, polyimide resins, aromatic polyamide resins, polyphenylene sulfide resins, etc. Resin materials (typically plastic materials) such as polyphenylene sulfide resins. The above materials can be materials constituting components of products such as electronic equipment. The double-sided adhesive sheet disclosed herein can be used by being attached to a component composed of the above-mentioned material. In addition, the above-mentioned material can be a material constituting a fixed object such as the above-mentioned pressure-sensitive sensor, display unit (for example, an electromagnetic wave shield, a reinforcing plate, and other back components). It should be noted that the fixed object refers to the object to which the double-sided adhesive sheet is attached, that is, the adherend. In addition, the back component refers to a component that is arranged on the opposite side of the surface (visual recognition side) of the above-mentioned pressure-sensitive sensor and display unit in a portable electronic device, for example, it can be a component that is arranged on the back side described later. Figure 4 The support portion 540 of the back side of the display device 500 shown in the figure may be a member of the support portion 540 of the back side of the display device 500 shown in the figure. In addition, the above-mentioned fixed object may be in any form of a single-layer structure or a multi-layer structure, and various surface treatments may be applied to the surface (adhesive surface) to which the double-sided adhesive sheet is attached. Although not particularly limited, as an example of a fixed object, a back member having a thickness of about 1 μm or more (typically about 5 μm or more, for example, about 60 μm or more, and further about 120 μm or more) and about 1500 μm or less (for example, about 800 μm or less) may be cited.
[0242] In some embodiments, the components and materials to which the double-sided adhesive sheet is pasted may be components and materials with light transmittance (translucent adherends). The adhesive surface of the double-sided adhesive sheet pasted on the translucent adherend can be visually recognized across the translucent adherend, so it is desirable to have an adhesive surface with good appearance quality. The light transmittance of the above-mentioned translucent adherend is, for example, greater than 50%, and may be greater than 70%. In some preferred embodiments, the light transmittance of the above-mentioned adherend is greater than 80%, more preferably greater than 90%, and may be greater than 95% (for example, 95% to 100%). Such a material may be a resin film (for example, a polyester resin film such as a PET film) disposed on the back of the image display portion of various devices such as portable electronic devices. The double-sided adhesive sheet disclosed herein may preferably be used in a manner of pasting on an adherend (for example, a component) having a light transmittance greater than a specified value as described above. The above-mentioned light transmittance refers to the light transmittance at a wavelength of 550nm.
[0243] In addition, in some embodiments, the double-sided adhesive sheet is used in a manner of being adhered to a metal component. As the material of the metal component, the metal materials exemplified as the above-mentioned adherend materials can be cited. The metal component is, for example, a component or article having a surface (adhesive sheet adhering surface) formed of a metal material such as aluminum or stainless steel. As a preferred example, metal components such as stainless steel components and aluminum components can be cited. The double-sided adhesive sheet can cover the entire surface of the metal component, or it can cover a portion of the above surface (for example, a portion of the area that needs to be masked). The above-mentioned metal component can, for example, constitute the later-mentioned Figure 4 The metal member is preferably an adherend on one side of the double-sided adhesive sheet.
[0244] As described above, a laminate is provided according to the technology disclosed herein, which has a double-sided adhesive sheet and a member pasted with the double-sided adhesive sheet. In some ways, the laminate comprising a double-sided adhesive sheet is a laminate having the double-sided adhesive sheet and a metal member (first member). The laminate may have a metal member and a double-sided adhesive sheet covering at least a portion of the surface of the metal member. The double-sided adhesive sheet may cover the entire surface of the metal member, or may cover a portion of the above-mentioned surface (for example, a portion of the area requiring masking). Typically, one side (adhesive surface) of the above-mentioned double-sided adhesive sheet is pasted on the above-mentioned metal member. In addition, in some ways, the member pasted with a double-sided adhesive sheet may have the light transmittance of the above-mentioned adherend material. In this way, the laminate comprising a double-sided adhesive sheet is a laminate having the double-sided adhesive sheet and a member (second member) with light transmittance. In addition, in some preferred ways, the laminate is a laminate having a metal member (first member), a double-sided adhesive sheet and a member (second member) with light transmittance in sequence. In addition, the substrate-less double-sided pressure-sensitive adhesive sheet is also referred to as a pressure-sensitive adhesive layer in the laminate.
[0245] The configuration of the above-mentioned laminate is shown in Figure 3 middle. Figure 3 The laminate 50 shown has a first component 41, a double-sided adhesive sheet 1 without a substrate, and a second component 42 in sequence. Specifically, in the laminate 50, one adhesive surface (first adhesive surface) 1A of the double-sided adhesive sheet 1 without a substrate is bonded to the first component 41, and the other adhesive surface (second adhesive surface) 1B of the double-sided adhesive sheet 1 is bonded to the second component 42. In this embodiment, the first component 41 and the second component 42 both have a sheet-like or plate-like shape, and the laminate 50 has a multilayer structure. In addition, in this embodiment, the first component 41 is a metal component, and the second component 42 is a light-transmitting component. The details of the components constituting the laminate are as described as the above-mentioned components, materials, and adherends, so no repeated description is given.
[0246] In some embodiments, the double-sided adhesive sheet is preferably used in electronic devices including various light sources such as LEDs (light emitting diodes), self-luminous organic electroluminescent elements, etc. For example, it can be preferably used in electronic devices (typically portable electronic devices) having organic electroluminescent display devices and liquid crystal display devices that require specified optical characteristics.
[0247] Figure 4 FIG. 1 is a perspective exploded view schematically showing an example of the structure of a display device. Figure 4 As shown, the display device 500 of the portable electronic device 400 has a display portion 520 and a support portion 540 composed of a cover member, an organic EL unit, etc. The display device 500 is configured by further including a double-sided adhesive sheet 530. In this configuration example, the double-sided adhesive sheet 530 fixes the components constituting the display portion 520 and the support portion 540. It should be noted that the support portion 240 is configured by including a substrate (a metal plate such as a stainless steel plate, an aluminum plate, etc.). The adhesive sheet disclosed herein is preferably used as a constituent element of the display device as described above.
[0248] In addition, in some embodiments, the double-sided adhesive sheet disclosed herein may have an adhesive layer containing an acrylic polymer with a high biomass carbon ratio, so that it can be used as a substitute for the acrylic adhesive in various applications using conventional acrylic adhesives (i.e., acrylic adhesives with a low biomass carbon ratio), which can help to suppress dependence on fossil resource materials. The double-sided adhesive sheet disclosed herein can be preferably used as a double-sided adhesive sheet with reduced dependence on fossil resource materials.
[0249] The matters disclosed in this specification include the following.
[0250] [1] A portable electronic device, wherein a double-sided adhesive sheet is adhered to a member constituting the portable electronic device, the double-sided adhesive sheet having an adhesive layer comprising an acrylic polymer, the acrylic polymer being a polymer of a monomer component comprising heptyl acrylate and a carboxyl-containing monomer, the monomer component comprising 3 wt % or more of the carboxyl-containing monomer, the adhesive layer having a gel fraction greater than 40%, a storage modulus of the adhesive layer at 23° C. of greater than 0.04 MPa, and a tan δ of greater than 0.46 at 23° C., wherein tan δ refers to a ratio (G” / G’) of a loss modulus G” of the adhesive layer to a storage modulus G’.
[0251] [2] The portable electronic device according to [1] above, wherein the adhesive layer further contains a tackifier resin.
[0252] [3] The portable electronic device according to [1] or [2] above, wherein the tackifier resin is at least one selected from a rosin-based tackifier resin and a terpene-based tackifier resin.
[0253] [4] The portable electronic device according to any one of [1] to [3] above, wherein the pressure-sensitive adhesive layer further contains an acrylic oligomer.
[0254] [5] The portable electronic device according to any one of [1] to [4] above, wherein the pressure-sensitive adhesive layer contains a tackifier resin and an acrylic oligomer.
[0255] [6] The portable electronic device according to [5] above, wherein the content of the tackifying resin is C T Relative to the content C of the acrylic oligomer O The ratio (C T / C O ) is greater than or equal to 1 and less than or equal to 10.
[0256] [7] The portable electronic device according to any one of [1] to [6] above, wherein the adhesive composition used to form the adhesive layer contains at least an isocyanate crosslinking agent.
[0257] [8] The portable electronic device according to any one of [1] to [7] above, wherein the thickness of the adhesive layer is greater than 5 μm and less than or equal to 50 μm.
[0258] [9] The portable electronic device according to any one of [1] to [8] above, wherein the double-sided adhesive sheet has a 180-degree peel strength with respect to a stainless steel plate of 10 N / 25 mm or more.
[0259]
[11] A double-sided adhesive sheet, comprising an adhesive layer comprising an acrylic polymer, wherein the acrylic polymer is a polymer of a monomer component comprising heptyl acrylate and a carboxyl-containing monomer, the monomer component comprising 3 wt % or more of the carboxyl-containing monomer, the gel fraction of the adhesive layer is greater than 40%, the storage modulus of the adhesive layer at 23° C. is greater than 0.04 MPa, and tan δ at 23° C. is greater than 0.46, wherein tan δ refers to the ratio of the loss modulus G” to the storage modulus G’ of the adhesive layer (G” / G’).
[0260]
[12] The double-sided PSA sheet according to
[11] above, wherein the PSA layer further contains a tackifier resin.
[0261]
[13] The double-sided PSA sheet according to
[11] or
[12] above, wherein the tackifier resin is at least one selected from the group consisting of a rosin-based tackifier resin and a terpene-based tackifier resin.
[0262]
[14] The double-sided PSA sheet according to any one of
[11] to
[13] above, wherein the PSA layer further contains an acrylic oligomer.
[0263]
[15] The double-sided PSA sheet according to any one of
[11] to
[14] above, wherein the PSA layer contains a tackifier resin and an acrylic oligomer.
[0264]
[16] The double-sided PSA sheet according to
[15] above, wherein the content of the tackifier resin is C T Relative to the content C of the acrylic oligomer O The ratio (C T / C O ) is greater than or equal to 1 and less than or equal to 10.
[0265]
[17] The double-sided PSA sheet according to any one of
[11] to
[16] above, wherein the PSA composition used to form the PSA layer contains at least an isocyanate crosslinking agent.
[0266]
[18] The double-sided PSA sheet according to any one of
[11] to
[17] above, wherein the PSA layer has a thickness greater than 5 μm and less than or equal to 50 μm.
[0267]
[19] The double-sided adhesive sheet according to any one of
[11] to
[18] above, wherein the double-sided adhesive sheet has a 180-degree peel strength against a stainless steel plate of 10 N / 25 mm or more.
[0268]
[20] The double-sided adhesive sheet according to any one of
[11] to
[19] above, wherein the double-sided adhesive sheet is used for fixing components in electronic devices.
[0269]
[21] An electronic device comprising the double-sided pressure-sensitive adhesive sheet according to any one of
[11] to
[20] above.
[0270]
[22] A double-sided PSA sheet with a release liner, comprising the double-sided PSA sheet according to any one of
[11] to
[20] above, and a release liner laminated on the adhesive surface of the double-sided PSA sheet.
[0271]
[23] A roll of a double-sided PSA sheet with a release liner, wherein the double-sided PSA sheet with a release liner is obtained by rolling up the double-sided PSA sheet with a release liner according to
[22] above.
[0272]
[31] A laminate comprising a metal component (first component) and a double-sided adhesive sheet, wherein the double-sided adhesive sheet has an adhesive layer comprising an acrylic polymer, the acrylic polymer being a polymer of a monomer component comprising heptyl acrylate and a carboxyl-containing monomer, the monomer component comprising 3 wt % or more of the carboxyl-containing monomer, the gel fraction of the adhesive layer being greater than 40%, the storage modulus of the adhesive layer at 23° C. being greater than 0.04 MPa, and the tan δ at 23° C. being greater than 0.46, wherein the tan δ refers to the ratio of the loss modulus G” to the storage modulus G’ of the adhesive layer (G” / G’).
[0273]
[32] A laminate comprising a light-transmitting member (second member) and a double-sided adhesive sheet, wherein the double-sided adhesive sheet has an adhesive layer comprising an acrylic polymer, the acrylic polymer being a polymer of a monomer component comprising heptyl acrylate and a carboxyl-containing monomer, the monomer component comprising 3 wt % or more of the carboxyl-containing monomer, the gel fraction of the adhesive layer being greater than 40%, the storage modulus of the adhesive layer at 23° C. being greater than 0.04 MPa, and the tan δ at 23° C. being greater than 0.46, wherein the tan δ refers to the ratio (G” / G’) of the loss modulus G” to the storage modulus G’ of the adhesive layer.
[0274]
[33] A laminated body comprising, in sequence, a metal component (first component), a double-sided adhesive sheet and a light-transmitting component (second component), wherein the double-sided adhesive sheet has an adhesive layer comprising an acrylic polymer, the acrylic polymer being a polymer of a monomer component comprising heptyl acrylate and a carboxyl-containing monomer, the monomer component comprising 3 wt % or more of the carboxyl-containing monomer, the adhesive layer having a gel fraction greater than 40%, a storage modulus of greater than 0.04 MPa at 23° C., and a tan δ of greater than 0.46 at 23° C., wherein tan δ refers to the ratio of the loss modulus G” to the storage modulus G’ of the adhesive layer (G” / G’).
[0275]
[34] The laminate according to
[31] or
[33] above, wherein the metal member is an aluminum member or a stainless steel member.
[0276]
[35] The laminated body described in
[32] or
[33] above, wherein the light transmittance of the light-transmitting member is greater than 50%.
[0277]
[36] The laminated body described in
[32] ,
[33] or
[35] above, wherein the light-transmitting member includes a resin film.
[0278]
[37] The laminate according to any one of
[31] to
[35] above, wherein the laminate is used in electronic equipment.
[0279] Example
[0280] Hereinafter, some embodiments of the present invention will be described, but it is not intended to limit the present invention to the contents shown in these embodiments. It should be noted that, unless otherwise specified, in the following description, "parts" and "%" are weight references.
[0281] <Example 1>
[0282] (Synthesis of acrylic polymer)
[0283] In a reaction vessel equipped with a stirrer, a thermometer, a nitrogen inlet tube, a reflux condenser and a dropping funnel, 93 parts of n-heptyl acrylate (n-HpA) and 7 parts of acrylic acid (AA) as monomer components and ethyl acetate as a polymerization solvent were added, and stirred for 2 hours while introducing nitrogen. By doing so, the oxygen in the polymerization system was removed, and then 0.2 parts of 2,2'-azobisisobutyronitrile (AIBN) was added as a polymerization initiator, and solution polymerization was carried out at 60°C to 70°C for 8 hours to obtain a solution of an acrylic polymer. The weight average molecular weight (Mw) of the acrylic polymer is 900,000. The adjustment of Mw is carried out by adjusting the concentration of the monomer components during polymerization. It should be noted that the above-mentioned n-HpA is a compound synthesized using heptol from biomass and having a heptyl group from biomass at the ester end.
[0284] (Preparation of Adhesive Composition)
[0285] To the acrylic polymer solution obtained above, 20 parts of a terpene phenol resin (trade name "YS POLYSTER T-115", a terpene phenol resin manufactured by Yasuhara Chemical Co., Ltd., softening point of about 115° C., hydroxyl value of 30 mgKOH / g to 60 mgKOH / g) as a tackifier resin, 5 parts of an acrylic oligomer, 3 parts of an isocyanate crosslinking agent A (trade name "CORONATE L", a 75% ethyl acetate solution of a trimethylolpropane / toluene diisocyanate trimer adduct, manufactured by Tosoh Corporation) and 0.02 parts of an epoxy crosslinking agent (trade name "TETRAD-C", 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, manufactured by Mitsubishi Gas Chemical Co., Ltd.) were added (based on solid content) with respect to 100 parts of the acrylic polymer contained in the solution, and the mixture was stirred and mixed to prepare the adhesive composition of this example.
[0286] As the acrylic oligomer, an acrylic oligomer prepared by the following method was used. Specifically, 95 parts of cyclohexyl methacrylate (CHMA) and 5 parts of AA, 10 parts of AIBN as a polymerization initiator, and ethyl acetate as a polymerization solvent were added to a reaction container equipped with a stirrer, a thermometer, a nitrogen inlet tube, a reflux condenser, and a dropping funnel, and stirred for 1 hour in a nitrogen stream to remove oxygen in the polymerization system, and then the temperature was raised to 85° C. and reacted for 5 hours to obtain an acrylic oligomer with a solid content concentration of 50%. The Mw of the obtained acrylic oligomer was 3600.
[0287] (Production of double-sided adhesive sheets)
[0288] The obtained adhesive composition was applied to the release surface of a polyester release liner (trade name "Diafoil MRF", manufactured by Mitsubishi Chemical Corporation) with a thickness of 38 μm, and dried at 100°C for 2 minutes to form an adhesive layer with a thickness of 35 μm. The release surface of a polyester release liner (trade name "Diafoil MRF", manufactured by Mitsubishi Chemical Corporation) with a thickness of 25 μm was attached to the adhesive layer. By doing so, a substrate-free double-sided adhesive sheet with a release liner protected on both sides by the above two polyester release liners was obtained.
[0289] <Example 2 to Example 9 and Comparative Examples 1 to 3>
[0290] The PSA compositions of each example were prepared by the same method as in Example 1 except that the monomer composition, Mw, amount of tackifier resin, amount of acrylic oligomer, type and amount of crosslinking agent, and thickness of PSA layer of the acrylic polymer were changed as shown in Table 1, and the obtained PSA compositions were used to prepare substrate-free double-sided PSA sheets with release liner of each example in the same manner as in Example 1. The Mw of the acrylic polymer was adjusted by adjusting the concentration of the monomer components during polymerization.
[0291] It should be noted that in Table 1, BA represents n-butyl acrylate. In addition, in Table 1, the isocyanate crosslinking agent B represents the isocyanurate of hexamethylene diisocyanate (manufactured by Tosoh Corporation, trade name "CORONATE HX", a 1% ethyl acetate solution of a trifunctional isocyanate compound), and the contents shown in Table 1 represent the contents of solid components (non-volatile components).
[0292] <Example 10>
[0293] Prepare the adhesive composition prepared by the method described in Example 1, apply the above-mentioned adhesive composition to a surface (first side) of a PET film (trade name "Lumirror", manufactured by Toray) with a thickness of 2 μm as a substrate layer, and dry it for 2 minutes at 100 ° C, thereby forming a first adhesive layer with a thickness of 35 μm. The release surface of a polyester release liner (trade name "Diafoil MRF", manufactured by Mitsubishi Chemical Corporation) with a thickness of 25 μm is attached to the above-mentioned first adhesive layer. In addition, prepare a polyester release liner (trade name "Diafoil MRF", manufactured by Mitsubishi Chemical Corporation) with a thickness of 38 μm, apply the above-mentioned adhesive composition to the release surface of the above-mentioned release liner, and dry it for 2 minutes at 100 ° C, thereby forming a second adhesive layer with a thickness of 35 μm. The second adhesive layer is transferred to the non-forming surface of the adhesive layer of the substrate layer formed with the first adhesive layer. By doing so, a double-sided adhesive sheet with a release liner of this example (double-sided adhesive sheet with substrate) was prepared.
[0294] <Evaluation method>
[0295] (Adhesion to SUS)
[0296] Under the measuring environment of 23°C and 50%RH, a PET film with a thickness of 50 μm was pasted on one adhesive surface of the double-sided adhesive sheet for lining, and the film was cut into a size of 25 mm in width and 100 mm in length, thereby preparing a measuring sample. Under the environment of 23°C and 50%RH, a 2 kg roller was reciprocated once, and the other adhesive surface of the measuring sample was pressed against the surface of a stainless steel plate (SUS304BA plate) washed with ethyl acetate. It was placed under the same environment for 72 hours, and then the peel strength (adhesion to SUS) [N / 25mm] was measured using a universal tensile compression tester according to JIS Z 0237:2000 at a tensile speed of 300 mm / min and a peeling angle of 180 degrees. In the measurement of the above peel strength, as a universal tensile compression tester, a "tensile compression tester, TG-1kN" manufactured by Minebea or its equivalent can be used.
[0297] (Punching processability)
[0298] The double-sided adhesive sheet with a release liner is cut to a specified size and used as an evaluation sample. A processing blade is inserted from one release liner (release liner on the light release side) side of the evaluation sample, and the processing (cutting) is to the depth of half-cutting the other release liner (release liner on the heavy release side) on the opposite side, and the outer shape of 25mm×25mm is processed into a frame with a width of 2mm, and the part other than the frame-shaped adhesive sheet is removed. After 60 seconds, the above-mentioned one release liner is removed from the double-sided adhesive sheet, and the protrusion degree of the adhesive at the processing end face of the exposed double-sided adhesive sheet is observed under a microscope. The situation where the protrusion of the adhesive of more than 0.1mm is confirmed is evaluated as "×", and the situation where the protrusion of the adhesive is less than 0.1mm is evaluated as "○". For each example, 10 evaluation samples are made, 10 evaluation tests are carried out (N=10), and the number of evaluation tests evaluated as ○ is X ( / 10) as the evaluation result of punching processability. If the number of evaluation tests evaluated as ○ is 5 or more (i.e., more than 5 / 10), it is judged to be qualified.
[0299] (Concave-convex deformation evaluation)
[0300] The double-sided adhesive sheet with release liner of each example (the laminate of release liner / double-sided adhesive sheet / release liner on the light release side) was wound under the same conditions under the same environment and formed into a roll body. After a specified time, it was rolled out from the roll body and cut into a size of 500mm×1000mm, thereby obtaining an evaluation sample. Under a clean room environment, the back of the release liner on the heavy release side was wiped with a wiping cloth (manufactured by Nippon Paper Co., Ltd.), and after removing foreign matter, the release liner on the light release side was peeled off from the evaluation sample. After 1 hour, at the midpoint between the point light source and the projection screen configured in a manner of about 100cm (a position about 50cm away from the point light source), the evaluation sample was kept in a planar shape, and the angle of the exposed adhesive layer surface of the evaluation sample was configured in a manner of about 90 degrees relative to the light from the point light source. Regarding the evaluation sample, the adhesive layer surface after the release liner on the light release side was peeled off was configured on the above-mentioned point light source side. In a dark room at 23°C and 50% RH, light the point light source, visually observe the image projected on the screen through the evaluation sample, and evaluate the presence or absence of concave-convex deformation (specifically, concave-convex deformation on the surface of the adhesive layer). As a point light source, for example, a "xenon lamp C2577" manufactured by Hamamatsu Photonics Co., Ltd. can be used. For each example, 10 evaluation samples were prepared and 10 evaluation tests were conducted (N=10), and the number of evaluation tests (qualified) in which concave-convex deformation was not confirmed, X( / 10), was used as the result of the concave-convex deformation evaluation. If the qualified number is 6 or more (i.e., 6 / 10 or more), it is determined that the fine concave-convex deformation is alleviated.
[0301] Table 1 shows the summary and evaluation results of each example.
[0302]
[0303] As shown in Table 1, the adhesives of Examples 1 to 10 contain an acrylic polymer, which contains heptyl acrylate as a monomer component and more than 3% of a carboxyl-containing monomer. The gel fraction of the adhesive is greater than 40%, the storage modulus at 23°C is greater than 0.04 MPa, and the tanδ at 23°C is greater than 0.46. The double-sided adhesive sheet containing the above adhesive has high adhesion to SUS, good punching processability, and excellent relaxation of fine concave and convex deformation. In contrast, the tanδ at 23°C of Comparative Examples 1 and 2 using BA-based polymers is less than 0.46, and the relaxation of concave and convex deformation is poor. In addition, although Comparative Example 1 has high adhesion to SUS, the gel fraction is 40%, and the evaluation result of punching processability is poor. The result of Comparative Example 2 is that the gel fraction and 23°C storage modulus are increased relative to Comparative Example 1, the punching processability is improved, but the adhesion is reduced. In addition, Comparative Example 3 used an acrylic polymer containing heptyl acrylate as a monomer component in the same manner as in the above-mentioned Examples, but the adhesive force, punching processability, and uneven deformation relaxation were all inferior to those of the above-mentioned Examples. It is believed that in Comparative Example 3, the amount of the carboxyl group-containing monomer used in the acrylic polymer was less than 3%, and high adhesive force could not be obtained, the 23°C storage modulus was as low as less than 0.04 MPa, and therefore good punching processability could not be obtained, and the 23°C tanδ was as low as less than 0.46, resulting in poor uneven deformation relaxation.
[0304] As can be seen from the above, a double-sided adhesive sheet having an adhesive layer containing heptyl acrylate as a monomer component and an acrylic polymer containing 3% by weight or more of a carboxyl group-containing monomer, an adhesive layer having a gel fraction of more than 40%, a storage modulus of more than 0.04 MPa at 23°C, and a tanδ of more than 0.46 at 23°C can have high adhesive strength and can take into account both the relaxation of fine uneven deformation and processability.
[0305] Although specific examples of the present invention have been described in detail above, these are merely illustrative and do not limit the scope of the claims. The technology described in the claims includes various modifications and changes to the specific examples described above.
[0306] Description of symbols
[0307] 1, 2, 530 double-sided adhesive sheet
[0308] 1A First bonding surface
[0309] 1B Second adhesive surface
[0310] 10 Support substrate
[0311] 10A first side
[0312] 10B Side 2
[0313] 21 Adhesive layer (first adhesive layer)
[0314] 21A bonding surface (first bonding surface)
[0315] 21B Second adhesive surface
[0316] 22 Adhesive layer (second adhesive layer)
[0317] 22A bonding surface (second bonding surface)
[0318] 31, 32 Release liner
[0319] 41 First Component
[0320] 42 Second component
[0321] 50 layers
[0322] 100, 200 Double-sided adhesive sheet with release liner
[0323] 150 cores
[0324] 300 Double-sided adhesive sheet roll with release liner
[0325] 400 Portable electronic devices
[0326] 500 display devices
[0327] 520 Display
[0328] 540 support
Claims
1. A double-sided adhesive sheet comprising an adhesive layer containing an acrylic polymer, wherein: The acrylic polymer is a polymer containing monomer components of heptyl acrylate and a carboxyl group-containing monomer. The monomer component contains 3% by weight or more of the carboxyl group-containing monomer, The gel fraction of the adhesive layer is greater than 40%, The adhesive layer has a storage modulus of 0.04 MPa or more at 23° C. and a tan δ of 0.46 or more at 23° C., where tan δ refers to a ratio (G” / G’) of a loss modulus G” to a storage modulus G’ of the adhesive layer.
2. The double-sided adhesive sheet according to claim 1, wherein The adhesive layer further comprises a tackifying resin.
3. The double-sided adhesive sheet according to claim 2, wherein The tackifying resin is at least one selected from rosin-based tackifying resins and terpene-based tackifying resins.
4. The double-sided pressure-sensitive adhesive sheet according to any one of claims 1 to 3, wherein The adhesive layer further includes an acrylic oligomer.
5. The double-sided pressure-sensitive adhesive sheet according to any one of claims 1 to 4, wherein The adhesive layer includes a tackifying resin and an acrylic oligomer.
6. The double-sided adhesive sheet according to claim 5, wherein The content of the tackifying resin C T Relative to the content C of the acrylic oligomer O The ratio (C T / C O ) is greater than or equal to 1 and less than or equal to 10.
7. The double-sided pressure-sensitive adhesive sheet according to any one of claims 1 to 6, wherein The adhesive composition for forming the adhesive layer contains at least an isocyanate-based cross-linking agent.
8. The double-sided pressure-sensitive adhesive sheet according to any one of claims 1 to 7, wherein The thickness of the adhesive layer is greater than 5 μm and less than or equal to 50 μm.
9. The double-sided pressure-sensitive adhesive sheet according to any one of claims 1 to 8, wherein The double-sided adhesive sheet has a 180-degree peel strength against a stainless steel plate of 10 N / 25 mm or more.
10. The double-sided pressure-sensitive adhesive sheet according to any one of claims 1 to 9, wherein The double-sided adhesive sheet is used for fixing components in electronic devices.
Citation Information
Patent Citations
Information processing device and data processing method
JP2022145688A
Adhesive agent, adhesive tape, electrical appliance, onboard member, and securing method
WO2021125247A1
Adhesive agent composition, adhesive tape, affixing method for electronic device component or in-vehicle component, and production method for electronic device component or in-vehicle component
WO2021125278A1